Antenna system including polymer composition having low dielectric loss tangent - Patents.com
A polymer composition with specific thermal and mechanical properties, integrated with laser-activated additives, addresses the challenge of miniaturizing 5G antennas by enhancing signal efficiency and performance in high-frequency applications.
Patent Information
- Application Number
- JP2022506886
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-27
- Filing Date
- 2020-08-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-08-19
AI Technical Summary
The challenge of miniaturizing 5G antennas while maintaining high-frequency performance is hindered by the limitations of existing materials, which affect signal transmission and reception efficiency.
A 5G antenna system utilizing a polymer composition with a glass transition temperature of 30°C or more and a dielectric constant of 0.1 or less, combined with laser-activated additives, enables the formation of substrates for antenna elements that support high-frequency signal transmission and reception with reduced size and improved performance.
The polymer composition allows for the creation of compact 5G antennas with low dielectric loss, high mechanical strength, and excellent processing characteristics, facilitating efficient signal transmission and reception across various temperature ranges.
Smart Images

Figure 0007623349000028 
Figure 0007623349000029 
Figure 0007623349000030
Abstract
Description
[Technical field]
[0001] Cross-reference of related questions
[0001] This application is incorporated herein by reference in its entirety, in accordance with U.S. Provisional Patent Application No. 62 / 889,792, having a filing date of August 21, 2019; U.S. Provisional Patent Application No. 62 / 898,188, having a filing date of September 10, 2019; U.S. Provisional Patent Application No. 62 / 925,274, having a filing date of October 24, 2019; U.S. Provisional Patent Application No. 62 / 951,039, having a filing date of December 20, 2019; U.S. Provisional Patent Application No. 62 / 952,039, having a filing date of February 10, 2020; No. 62 / 972,195, having a filing date of March 25, 2020; U.S. Provisional Patent Application No. 62 / 994,314, having a filing date of April 13, 2020; U.S. Provisional Patent Application No. 63 / 008,979, having a filing date of May 14, 2020; U.S. Provisional Patent Application No. 63 / 024,557, having a filing date of June 15, 2020; U.S. Provisional Patent Application No. 63 / 038,959, having a filing date of June 15, 2020; and U.S. Provisional Patent Application No. 63 / 056,842, having a filing date of July 27, 2020. [Background technology]
[0002]
[0002] High frequency wireless signal communication is gaining more and more popularity. For example, the demand for faster data transmission for wireless smartphone connectivity is driving demand for high frequency components, including those configured to operate at 5G spectrum frequencies. Transmitting and receiving at such frequencies generally requires antennas with smaller feature sizes. The trend towards miniaturization makes small high frequency 5G antennas even more desirable. 5G antennas can utilize a variety of materials. However, the properties of such materials can limit the miniaturization of 5G antennas and / or adversely affect the high frequency performance of 5G antennas. Summary of the Invention [Problem to be solved by the invention]
[0003]
[0003] Therefore, there is a need for high performance materials for 5G antennas to achieve miniaturization and improved antenna performance. [Means for solving the problem]
[0004] According to one embodiment of the present invention, a 5G antenna system is disclosed that includes a substrate and at least one antenna element configured to transmit and receive 5G radio frequency signals. The antenna element is bonded to the substrate. The substrate includes a polymer composition including a polymer matrix containing at least one polymer having a glass transition temperature of about 30° C. or more and at least one laser activatable additive, the polymer composition exhibiting a dielectric loss tangent of about 0.1 or less determined at a frequency of 2 GHz.
[0005]
[0005] Other features and aspects of the present invention are described in more detail below.
[0006] A full and enabling disclosure of the present invention, including the best mode thereof, to one of ordinary skill in the art, is set forth more particularly in the remainder of the specification, including reference to the accompanying drawings, in which: [Brief description of the drawings]
[0006] [Figure 1]
[0007] FIG. 1 is a diagram of a 5G antenna system including a base station, one or more relay stations, one or more user computing devices, and one or more Wi-Fi repeaters according to an embodiment of the present disclosure. [Figure 2A]
[0008] FIG. 1 illustrates a top view of an exemplary user computing device including a 5G antenna in accordance with an aspect of the present disclosure. [Figure 2B]
[0009] FIG. 2B is a side view of the example user computing device of FIG. 2A including a 5G antenna according to an embodiment of the present disclosure. [Diagram 3]
[0010] FIG. 2B is an expanded view of a portion of the user computing device of FIG. 2A. [Figure 4]
[0011] FIG. 1 is a side view of a coplanar waveguide antenna array configuration according to an aspect of the present disclosure. [Figure 5A]
[0012] FIG. 2 is a diagram of an antenna array for a massive multiple-in-multiple-out configuration according to an aspect of the present disclosure. [Figure 5B]
[0013] FIG. 1 is a diagram of an antenna array formed by laser direct structuring according to an aspect of the present disclosure. [Figure 5C]
[0014] FIG. 1 is a diagram of an exemplary antenna configuration according to an aspect of the present disclosure. [Figure 6A]
[0015] FIG. 6A is a simplified sequence diagram of a laser direct structuring manufacturing method that can be used to form antenna elements and / or arrays according to an embodiment of the present disclosure. [Figure 6B] FIG. 6B is a simplified sequence diagram of a laser direct structuring manufacturing method that can be used to form antenna elements and / or arrays according to embodiments of the present disclosure. [Figure 6C] FIG. 6C is a simplified sequence diagram of a laser direct structuring manufacturing method that can be used to form antenna elements and / or arrays according to embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007]
[0016] It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.
[0017] In general, the present invention relates to a 5G antenna system including a substrate and at least one antenna element configured to transmit and receive 5G radio frequency signals, the at least one antenna element being coupled to the substrate. The substrate is formed from a polymer composition including a polymer matrix containing at least one polymer having a glass transition temperature of about 30° C. or greater and at least one laser activatable additive, the polymer composition exhibiting a dielectric loss tangent of about 0.1 or less determined at a frequency of 2 GHz.
[0008]
[0018] In this regard, the polymer composition has desirable dielectric properties that enable its use in antenna systems. For example, the dissipation factor, a measure of the rate of energy loss of the polymer composition, may be relatively low, which can assist in optimizing signal loss when utilized in certain applications, such as signal transmission applications, particularly those related to 5G communications. In this regard, the dissipation factor may be about 0.1 or less, in some embodiments about 0.05 or less, in some embodiments about 0.01 or less, in some embodiments about 0.0001 to about 0.008, and in some embodiments about 0.0002 to about 0.006 at typical 5G frequencies (e.g., 2 or 10 GHz). Indeed, in some cases the dissipation factor may be very low, such as about 0.003 or less, in some embodiments about 0.002 or less, in some embodiments about 0.001 or less, in some embodiments about 0.0009 or less, in some embodiments about 0.0008 or less, and in some embodiments about 0.0001 to about 0.0007 at typical 5G frequencies (e.g., 2 or 10 GHz).
[0009]
[0019] In addition to having a low dielectric loss tangent, in one embodiment, the polymer composition may exhibit a desired dielectric constant. The dielectric constant may be relatively high or relatively low depending on the particular use. Regardless of the application, the dielectric constant may enable the utilization of multiple conductive elements (e.g., antennas) operating simultaneously with only minimal levels of electrical interference. For example, in one embodiment, the polymer composition may exhibit a low dielectric constant of about 4 or less, in some embodiments about 3.9 or less, in some embodiments about 0.1 to about 3.8, in some embodiments about 1 to about 3.7, in some embodiments about 1.5 to about 3.6, in some embodiments about 2 to about 3.5, in some embodiments about 2.5 to about 3.4 at typical 5G frequencies (e.g., 2 or 10 GHz). However, in other embodiments, the polymer composition may exhibit a high dielectric constant of about 4 or more, in some embodiments about 4.5 or more, in some embodiments about 5 or more, in some embodiments about 8 or more, in some embodiments about 10 to about 40, in some embodiments about 15 to about 30 at typical 5G frequencies (e.g., 2 or 10 GHz). In particular, the inventors have also surprisingly discovered that the dielectric constant and dielectric loss tangent can be maintained within the above-mentioned ranges even when exposed to various temperatures, such as temperatures from about -30°C to about 100°C. For example, when subjected to the thermal cycling test described herein, the ratio of the dielectric constant after thermal cycling to the initial dielectric constant may be about 0.8 or more, in some embodiments about 0.9 or more, and in some embodiments about 0.91 to about 0.99. Similarly, the ratio of the dielectric loss tangent after exposure to high temperatures to the initial dielectric loss tangent may be about 1 or less, in some embodiments about 0.95 or less, in some embodiments about 0.1 to about 0.9, and in some embodiments about 0.2 to about 0.8. The change in dielectric loss tangent (i.e., initial dielectric loss tangent minus dielectric loss tangent after thermal cycling) may also range from about -0.1 to about 0.1, in some embodiments about -0.05 to about 0.01, and in some embodiments about -0.001 to 0.
[0010]
[0020] Traditionally, it was believed that polymer compositions exhibiting low dielectric tangents did not simultaneously have sufficiently good thermal, mechanical properties and ease of processing (i.e., low viscosity) to enable their use in certain types of applications. However, in contrast to conventional thinking, it has been found that polymer compositions have both excellent thermal, mechanical properties and processability. For example, the melting temperature of the polymer composition may be, for example, about 180°C or higher, about 200°C in some embodiments, about 210°C to about 400°C in some embodiments, and about 220°C to about 380°C in some embodiments. Even at such melting temperatures, the ratio of the temperature deflection under load ("DTUL") to the melting temperature, which is a measure of short-term heat resistance, may still remain relatively high. For example, the ratio may range from about 0.5 to about 1.00, from about 0.6 to about 0.95 in some embodiments, and from about 0.65 to about 0.85 in some embodiments. Certain DTUL values may be, for example, greater than about 200° C., and in some embodiments, between about 200° C. and about 350° C., and in some embodiments, between about 210° C. and about 320° C., and in some embodiments, between about 230° C. and about 290° C. Such high DTUL values may, among other things, enable the use of fast and reliable surface mounting processes for mating the structure and other components of the electrical component.
[0011]
[0021] The polymeric composition may also have good mechanical properties that may be useful in forming a substrate. For example, the polymeric composition may exhibit a tensile strength of about 10 MPa or more, in some embodiments about 50 MPa or more, in some embodiments about 70 MPa to about 300 MPa, and in some embodiments about 80 MPa to about 200 MPa. The polymeric composition may exhibit a tensile elongation of about 0.3% or more, in some embodiments about 0.4% or more, in some embodiments about 0.5% to about 4%, and in some embodiments about 0.5% to about 2%. The polymeric composition may exhibit a tensile modulus of about 5,000 MPa or more, in some embodiments about 6,000 MPa or more, in some embodiments about 7,000 MPa to about 25,000 MPa, and in some embodiments about 10,000 MPa to about 20,000 MPa. Tensile properties may be determined according to ISO Test No. 527:2012 at a temperature of 23°C.
[0012]
[0022] Further, the polymeric composition may exhibit a flexural strength of about 20 MPa or more, in some embodiments about 10 MPa or more, in some embodiments about 50 MPa or more, in some embodiments about 70 MPa to about 300 MPa, and in some embodiments about 80 MPa to about 200 MPa. The polymeric composition may exhibit a flexural elongation of about 0.4% or more, in some embodiments about 0.5% to about 4%, and in some embodiments about 0.5% to about 2%. The polymeric composition may exhibit a flexural modulus of about 5,000 MPa or more, in some embodiments about 6,000 MPa or more, in some embodiments about 7,000 MPa to about 25,000 MPa, and in some embodiments about 10,000 MPa to about 20,000 MPa. Flexural properties may be determined according to 178:2010 at a temperature of 23°C.
[0013]
[0023] Additionally, the polymer composition may also have high impact strength, which may be useful in forming thin substrates. For example, the polymer composition may have a strength of about 3 kJ / m 2 or more, in some embodiments, about 5 kJ / m 2 or more, in some embodiments, about 7 kJ / m 2 or more, in some embodiments, about 8 kJ / m 2 ~about 40kJ / m 2 , in some embodiments, about 10 kJ / m 2 ~about 25kJ / m 2 The impact strength may be determined in accordance with ISO Test No. ISO 179-1:2010 at a temperature of 23°C.
[0014]
[0024] As a result of the above-mentioned properties, the polymer composition can be readily formed into a substrate to which one or more conductive elements may then be applied, such as by using laser direct structuring ("LDS"). Due to the beneficial properties of the polymer composition, the resulting substrate may have a very small size, such as a thickness of about 5 millimeters or less, in some embodiments about 4 millimeters or less, and in some embodiments, from about 0.5 to about 3 millimeters.
[0015]
[0025] In particular, the substrate can be utilized in antennas. For example, the polymer composition may be utilized in high frequency antennas and antenna arrays used in base stations, repeaters (e.g., "femtocells"), relay stations, terminals, user devices, and / or other suitable components of 5G systems. As used herein, "5G" generally refers to high-speed data communication by radio frequency signals. 5G networks and systems can communicate data at much higher speeds than previous generations of data communication standards (e.g., "4G", "LTE"). Various standards and specifications have been published that quantify the requirements for 5G communication. As an example, the International Telecommunications Union (ITU) published the International Mobile Telecommunications-2020 ("IMT-2020") standard in 2015. The IMT-2020 standard defines various data transmission criteria (e.g., downlink and uplink data rates, latency, etc.) for 5G. The IMT-2020 standard specifies uplink and downlink peak data rates as the minimum data rates for uploading and downloading data that 5G systems must support. The IMT-2020 standard sets the downlink peak data rate requirement at 20 Gbit / s and the uplink peak data rate at 10 Gbit / s.
[0016]
[0026] As another example, rdThe Third Generation Partnership Project (3GPP) recently published a new standard for 5G, called "5G NR." 3GPP published "Release 15" in 2018, which specifies "Phase 1" as the standardization of 5G NR. 3GPP specifies the 5G frequency band as "Frequency Range 1" (FR1), which generally includes frequencies below 6 GHz, and "Frequency Range 2" (FR2), which is a frequency band in the range of 20-60 GHz. However, as used herein, "5G frequency" may refer to systems that utilize frequencies greater than 60 GHz, e.g., in the ranges up to 80 GHz, up to 150 GHz, and up to 300 GHz. As used herein, "5G frequency" may refer to a frequency of about 2.5 GHz or higher, and in some embodiments, about 3.0 GHz or higher, and in some embodiments, about 3 GHz to about 300 GHz or higher, and in some embodiments, about 4 GHz to about 80 GHz, and in some embodiments, about 5 GHz to about 80 GHz, and in some embodiments, about 20 GHz to about 80 GHz, and in some embodiments, about 28 GHz to about 60 GHz.
[0017]
[0027] The antenna elements / arrays and systems described herein may meet or be considered "5G" based on standards published by 3GPP such as Release 15 (2018) and / or IMT-2020 standards. To achieve such high-speed data communications at high frequencies, antenna elements and arrays typically utilize small feature sizes / spacings (e.g., fine pitch technology) and / or advanced materials that can improve antenna performance. For example, feature sizes (spacing between antenna elements, width of antenna elements), etc., typically depend on the wavelength ("λ") of the desired transmit and / or receive radio frequency propagating through the dielectric of the substrate on which the antenna elements are formed (e.g., nλ / 4, where n is an integer). Additionally, beamforming and / or beamsteering can be utilized to facilitate transmission and reception across multiple frequency ranges or channels (e.g., multiple-input multiple-output (MIMO), massive MIMO).
[0018]
[0028] The high frequency 5G antenna elements may have various configurations according to aspects of the present disclosure. For example, the 5G antenna elements may be or include coplanar waveguide elements, patch arrays (e.g., mesh grid patch arrays), other suitable 5G antenna configurations. The antenna elements may be configured to provide MIMO, massive MIMO capabilities, beam steering, etc.
[0019]
[0029] As used herein, "massive" MIMO capabilities generally refer to providing a large number of transmit and receive channels by an antenna array, for example, eight transmit (Tx) channels and eight receive (Rx) channels (abbreviated as 8×8). Massive MIMO capabilities may include 8×8, 12×12, 16×16, 32×32, 64×64, or more.
[0020]
[0030] The antenna elements may have various configurations and arrangements and may be fabricated using various manufacturing techniques. As an example, the antenna elements and / or associated elements (e.g., ground elements, feedlines, etc.) may utilize fine pitch technology. Fine pitch technology generally refers to small or fine spacing between their components or leads. For example, the feature size and / or spacing between antenna elements (or between antenna elements and ground planes) may be about 1,500 micrometers or less, in some embodiments 1,250 micrometers or less, in some embodiments 750 micrometers or less (e.g., center-to-center spacing of 1.5 mm or less), 650 micrometers or less, in some embodiments 550 micrometers or less, in some embodiments 450 micrometers or less, in some embodiments 350 micrometers or less, in some embodiments 250 micrometers or less, in some embodiments 150 micrometers or less, in some embodiments 100 micrometers or less, and in some embodiments 50 micrometers or less. However, it should be understood that smaller and / or larger feature sizes and / or spacings may be utilized within the scope of the present disclosure.
[0021]
[0031] As a result of such small feature sizes, antenna configurations and / or arrays having a large number of antenna elements within a small footprint can be achieved. For example, the antenna array may have an average antenna element density of more than 1,000 antenna elements per square centimeter, in some embodiments more than 2,000 antenna elements per square centimeter, in some embodiments more than 3,000 antenna elements per square centimeter, in some embodiments more than 4,000 antenna elements per square centimeter, in some embodiments more than 6,000 antenna elements per square centimeter, and in some embodiments more than about 8,000 antenna elements per square centimeter. Such a dense arrangement of antenna elements can provide a larger number of channels for MIMO functionality per unit area of antenna area. For example, the number of channels may correspond to (e.g., be equal to or proportional to) the number of antenna elements.
[0022]
[0032] 1, a 5G antenna system 100 may include a base station 102, one or more relay stations 104, one or more user computing devices 106, one or more Wi-Fi repeaters 108 (e.g., “femtocells”), and / or other suitable antenna components of a 5G antenna system 100. A relay station 104 may be connected to the base station 102 and the user computing devices 106 and / or a central The base station 102 may be configured to facilitate communication with the user computing devices 106 and / or other relay stations 104 by relaying or "repeat" signals between the relay stations 104. The base station 102 may include a MIMO antenna array 110 configured to receive and / or transmit radio frequency signals 112 with the relay stations 104, Wi-Fi repeaters 108, and / or directly with the user computing devices 106. 106 is not necessarily limited by the present invention and includes devices such as 5G smartphones.
[0023]
[0033] The MIMO antenna array 110 may utilize beam steering to focus or direct the radio frequency signals 112 towards the relay station 104. For example, the MIMO antenna array 110 may be configured to adjust an elevation angle 114 with respect to a heading angle 116 defined in the XY and / or ZY planes, as well as with respect to the Z direction.
[0024]
[0034] Similarly, one or more of the relay station 104, user computing device 106, and Wi-Fi repeater 108 may utilize beam steering to improve reception and / or transmission capabilities to the MIMO antenna array 110 of the base station 102 by directionally tuning the sensitivity and / or transmission of the devices 104, 106, 108 to the MIMO antenna array 110 of the base station 102 (e.g., by adjusting one or both of the relative elevation angle and / or relative azimuth angle of the respective devices).
[0025]
[0035] 2A and 2B are top and side views, respectively, of an exemplary user computing device 106. The user computing device 106 may include one or more antenna elements 200, 202 (e.g., arranged as an antenna array). With reference to FIG. 2A, the antenna elements 200, 202 may be configured to perform beam steering in the XY plane (indicated by arrows 204, 206, corresponding to relative azimuth angles). With reference to FIG. 2B, the antenna elements 200, 202 may be configured to perform beam steering in the ZY plane (indicated by arrows 204, 206).
[0026]
[0036] 3 is a simplified schematic diagram of multiple antenna arrays 302 connected (e.g., with a front-end module) using respective feed lines 304. The antenna arrays 302 may be mounted on a side 306 of a substrate 308, for example, as described and illustrated with respect to FIGS. 4A-4C. The antenna arrays 302 may include multiple vertically connected elements (e.g., a mesh grid array). Thus, the antenna arrays 302 may extend generally parallel to the side 306 of the substrate 308. A shield may optionally be provided on the side 306 of the substrate 308 such that the antenna arrays 302 are located outside the shield relative to the substrate 308.
[0027]
[0037] The vertical spacing between the vertically connected elements of the antenna array 302 is 302 Accordingly, in some embodiments, these spacing distances may be relatively small (e.g., less than about 750 micrometers) such that the antenna array 302 is a “fine pitch” antenna array 302.
[0028]
[0038] 4 is a side view of a configuration of a coplanar waveguide antenna 400 according to an embodiment of the disclosure. One or more coplanar ground layers 402 may be disposed parallel to an antenna element 404 (e.g., a patch antenna element). Another ground layer 406 may be spaced apart from the antenna element 404 by a substrate 408. One or more additional antenna elements 410 may be spaced apart from the antenna element 404 by a second layer or substrate 412.
[0029]
[0039] The dimensions "G" and "W" may correspond to a "feature size" of the antenna 400. The "G" dimension may correspond to the distance between the antenna element 404 and the coplanar ground plane 406. The "W" dimension may correspond to the width (e.g., line width) of the antenna element 404. Thus, in some embodiments, the dimensions "G" and "W" may be relatively small (e.g., less than about 750 micrometers) such that the antenna 400 is a "fine pitch" antenna 400.
[0030]
[0040] 5A is a diagram of an antenna array 500 according to an aspect of the disclosure. The antenna array 500 may include a substrate 510 and a plurality of antenna elements 520 formed thereon. The plurality of antenna elements 520 may be approximately uniformly sized in the X and / or Y directions (e.g., square or rectangular). The plurality of antenna elements 520 may be approximately uniformly spaced apart in the X and Y directions. The dimensions of and / or spacing between the antenna elements 520 may correspond to a "feature size" of the antenna array 500. Thus, in some embodiments, the dimensions and / or spacing may be relatively small (e.g., less than about 750 micrometers) such that the antenna array 500 is a "fine pitch" antenna array 500.
[0031]
[0041] 5 are shown by way of example only, as illustrated by the ellipses 522. Similarly, the number of rows of antenna elements 520 are shown by way of example only.
[0032]
[0042] The tuned antenna array 500 may be used, for example, to provide a base station with massive MIMO capabilities (e.g., as described above with respect to FIG. 1). More specifically, the radio frequency interactions between the various elements may be controlled or tuned to provide multiple transmit and / or receive channels. The transmit power and / or receive sensitivity may be directionally controlled to focus or direct the radio frequency signal, for example, as described with respect to the radio frequency signal 112 of FIG. 1.
[0033]
[0043] The tuned antenna array 500 can provide a large number of antenna elements 522 within a small footprint. For example, the tuned antenna 500 can have an average antenna element density of 1,000 or more antenna elements per square centimeter. Such a dense arrangement of antenna elements can provide a larger number of channels for MIMO functionality per unit area. For example, the number of channels can correspond to (e.g., be equal to or proportional to) the number of antenna elements.
[0034]
[0044] 5B is a diagram of an antenna array 540 formed by laser direct structuring according to an embodiment of the present disclosure. The antenna array 540 may include a number of antenna elements 542 and a number of feedlines 544 connecting the antenna elements 542 (e.g., with other antenna elements 542, front-end modules, or other suitable components). The antenna elements 542 each have a width "w" as well as a spacing distance "S" therebetween. 1 " and "S 2 (e.g., in the X-direction and Y-direction, respectively). These dimensions may be selected to achieve 5G frequency communication at a desired 5G frequency. More specifically, the dimensions may be selected to tune the antenna array 540 to transmit and / or receive data using radio frequency signals within the 5G frequency spectrum (e.g., greater than 2.5 GHz and / or greater than 3 GHz and / or greater than 28 GHz). The dimensions may be selected based on material properties of the substrate. For example, “w”, “S 1 " or "S 2 One or more of the " may correspond to a multiple of the propagation wavelengths ("λ") of the desired frequency through the substrate material (e.g., nλ / 4, where n is an integer).
[0035]
[0045] As an example, λ can be:
[0036]
number
[0037] (where c is the speed of light in a vacuum and ε R is the relative dielectric constant of the substrate (or surrounding material) and f is the desired frequency) It may be calculated as follows:
[0038]
[0046] 5C is a diagram of an exemplary antenna configuration 560 according to an embodiment of the present disclosure. The antenna configuration 560 may include multiple antenna elements 562 disposed on parallel long sides of a substrate 564. The various antenna elements 562 may have respective lengths "L" (and spacing distances therebetween) that tune the antenna configuration 560 to receive and / or transmit at a desired frequency and / or frequency range. More particularly, such dimensions may be selected based on a propagation wavelength λ at a desired frequency for the substrate material, e.g., as described above with reference to FIG. 5B.
[0039]
[0047] 6A-6C are simplified sequence diagrams of a laser direct structuring manufacturing method that can be used to form antenna elements and / or arrays according to embodiments of the present disclosure. With reference to FIG. 6A, a substrate 600 is formed using injection molding to form a desired shape. The substrate 600 may comprise a variety of materials, such as a polymeric composition containing a laser activatable additive.
[0040]
[0048] 6B, a laser 602 may be used to activate the laser activatable additive to form a circuit pattern 604, which may include one or more of the antenna elements and / or arrays. For example, the laser can melt conductive particles in the polymer composition to form the circuit pattern 604.
[0041]
[0049] Referring to FIG. 6C, the substrate 600 may be immersed in an electroless copper bath to plate circuit patterns 604 to form antenna elements, element arrays, other components and / or conductive lines therebetween.
[0042]
[0050] Various embodiments of the invention will now be described in more detail. I. Polymer Composition A. Polymer matrix
[0051] Generally, any of a variety of polymers or combinations of polymers may be utilized in the polymer matrix. For example, the polymer may be semi-crystalline or crystalline in nature. In one embodiment, the polymer may be semi-crystalline. In another embodiment, the polymer may be crystalline. Additionally, in one embodiment, the polymer may be an aromatic polymer. Alternatively, in another embodiment, the polymer may be an aliphatic polymer.
[0043]
[0052] Suitable polymers may include thermoplastic polymers, such as polyolefins (e.g., ethylene polymers, propylene polymers, etc.), polyamides (e.g., aliphatic, semi-aromatic, or aromatic polyamides), polyesters (e.g., polyethylene terephthalate, polybutylene terephthalate, liquid crystal polymers), polyarylene sulfides, polyetherimides, polyacetals (e.g., polyoxymethylene), polyphenylene oxides, polyaryl ketones (e.g., polyether ether ketones, polyether ketone ketones, etc.), polycarbonates, and the like, and blends thereof.
[0044]
[0053] Regardless, the polymers may generally be considered "high performance" polymers and thus may have relatively high glass transition temperatures and / or high melting temperatures. Such high performance polymers may thus impart a substantial degree of heat resistance to the polymer composition. For example, the polymers may have glass transition temperatures of about 30° C. or higher, in some embodiments about 40° C. or higher, in some embodiments from about 50° C. to about 250° C., and in some embodiments from about 60° C. to about 150° C. The polymers may also have melting temperatures of about 180° C. or higher, in some embodiments about 200° C. or higher, in some embodiments from about 210° C. to about 400° C., and in some embodiments from about 220° C. to about 380° C. Glass transition temperatures and melting temperatures may be determined as known in the art using differential scanning calorimetry ("DSC"), for example, by ISO Test Nos. 11357-2:2013 (glass transition temperature) and 11357-3:2011 (melting temperature).
[0045]
[0054] An example of a suitable semicrystalline aromatic polymer is an aromatic polyester, which is the condensation product of an aromatic dicarboxylic acid having, for example, 8 to 14 carbon atoms and at least one diol. Suitable diols include, for example, neopentyl glycol, cyclohexanedimethanol, 2,2-dimethyl-1,3-propanediol, and carboxylic acids of the formula HO(CH 2 ) nOH, where n is an integer from 2 to 10. Suitable aromatic dicarboxylic acids include, for example, isophthalic acid, terephthalic acid, 1,2-di(p-carboxyphenyl)ethane, 4,4'-dicarboxydiphenyl ether, and the like, and combinations thereof. Fused rings may be present, such as in 1,4-, or 1,5-, or 2,6-naphthalenedicarboxylic acid. Specific examples of such aromatic polyesters include, for example, poly(ethylene terephthalate) (PET), poly(1,4-butylene terephthalate) (PBT), poly(1,3-propylene terephthalate) (PPT), poly(1,4-butylene 2,6-naphthalate) (PBN), poly(ethylene 2,6-naphthalate) (PEN), poly(1,4-cyclohexylene dimethylene terephthalate) (PCT), and copolymers and mixtures of the above.
[0046]
[0055] In one particular embodiment, the polymer may comprise polybutylene terephthalate. The polybutylene terephthalate may have a crystallinity of about 38% or more, in some embodiments about 40% or more, and in some embodiments about 45% or more. The crystallinity of the polybutylene terephthalate polymer may generally be about 70% or less, in some embodiments about 65% or less, and in some embodiments about 60% or less. Percent crystallinity may be determined using differential scanning calorimetry (DSC). Such analysis may be performed using a PerkinElmer Pyris 6 DSC instrument. A detailed description of the calculations is available from Sichina, WJ, "DSC as problem solving tool: measurement of percent crystallinity of thermoplastics." Thermal Analysis Application Note (2000).
[0047]
[0056] Additionally, modifications or copolymers of polyethylene terephthalate and / or polybutylene terephthalate polymers may also be used. For example, in one embodiment, a modifying acid or modifying diol may be used to produce a modified polyethylene terephthalate and / or modified polybutylene terephthalate polymer. The terms "modifying acid" and "modifying diol" as used herein are intended to define compounds that can form part of the acid and diol repeat units of a polyester, respectively, and that can modify the polyester to reduce its crystallinity or render the polyester amorphous. Of course, the polyester may be unmodified and not contain a modifying acid or modifying diol. In either case, examples of the modifying acid component may include, but are not limited to, isophthalic acid, phthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, suberic acid, 1,12-dodecanedioic acid, and the like. In practice, it is often preferred to use functional acid derivatives of these, such as the dimethyl, diethyl, or dipropyl esters of the dicarboxylic acids. Where practical, the anhydrides or acid halides of these acids may also be utilized.Examples of modified diol components include, but are not limited to, neopentyl glycol, 1,4-cyclohexanedimethanol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, Z,8-bis(hydroxymethyltricyclo-[5.2.1.0]-decane (wherein Z represents 3, 4, or 5); 1,4-bis(2-hydroxyethoxy)benzene. benzene, 4,4'-bis(2-hydroxyethoxy)diphenyl ether [bis-hydroxyethyl bisphenol A], 4,4'-bis(2-hydroxyethoxy)diphenyl sulfide [bis-hydroxyethyl bisphenol S], and diols containing one or more oxygen atoms in the chain, such as diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, etc. Generally, these diols contain 2 to 18, and in some embodiments 2 to 8 carbon atoms. The alicyclic diols can be utilized in their cis or trans configurations, or as a mixture of both forms.
[0048]
[0057] In some embodiments, the at least one polyester or copolyester present in the polymer composition may have an intrinsic viscosity (IV) of about 0.5 to about 0.9 dL / g, such as about 0.5 to about 0.8 dL / g. In one embodiment, for example, the intrinsic viscosity of the polyester is about 0.65 to about 0.8 dL / g.
[0049]
[0058] Polyarylene sulfides are also suitable semi-crystalline aromatic polymers. The polyarylene sulfides utilized in the composition generally have the formula: -[(Ar 1 ) n -X] m -[(Ar 2 ) i -Y] j -[(Ar3 ) k -Z] l -[(Ar 4 ) o -W] p - (In the formula, Ar 1 , Ar 2 , Ar 3 and Ar 4 are independently arylene units of 6 to 18 carbon atoms; W, X, Y and Z are independently -SO 2 a divalent linking group selected from -, -S-, -SO-, -CO-, -O-, -C(O)O-, or an alkylene or alkylidene group of 1 to 6 carbon atoms, where at least one of the linking groups is -S-; n, m, i, j, k, l, o and p are independently 0, 1, 2, 3 or 4, provided that the sum of them is 2 or greater. It has the repeating unit:
[0050]
[0059] Arylene unit Ar 1 , Ar 2 , Ar 3 and Ar 4 may be optionally substituted or unsubstituted. Advantageous arylene units are phenylene, biphenylene, naphthylene, anthracene and phenanthrene. Polyarylene sulfides typically contain more than about 30 mol%, more than about 50 mol%, or more than about 70 mol% arylene sulfide (-S-) units. For example, polyarylene sulfides may contain at least 85 mol% of sulfide linkages directly bonded to two aromatic rings. In one particular embodiment, polyarylene sulfides as referred to herein have as their components the phenylene sulfide structure -(C 6 H 4 -S) n - (wherein n is an integer of 1 or greater).
[0051]
[0060] The synthesis techniques that may be used to make polyarylene sulfide are generally known in the art. For example, the method of producing polyarylene sulfide may include reacting a material that provides hydrosulfide ions (e.g., an alkali metal sulfide) with a dihaloaromatic compound in an organic amide solvent. The alkali metal sulfide may be, for example, lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, or a mixture thereof. If the alkali metal sulfide is a hydrate or an aqueous mixture, the alkali metal sulfide may be treated by a dehydration operation before the polymerization reaction. The alkali metal sulfide may also be generated in situ. In addition, a small amount of alkali metal hydroxide may be included in the reaction to remove or react (e.g., to convert such impurities into harmless materials), such as alkali metal polysulfides or alkali metal thiosulfates that may be present in very small amounts with the alkali metal sulfide.
[0052]
[0061] The dihaloaromatic compound may be, without limitation, an o-dihalobenzene, an m-dihalobenzene, a p-dihalobenzene, a dihalotoluene, a dihalonaphthalene, a methoxy-dihalobenzene, a dihalobiphenyl, a dihalobenzoic acid, a dihalodiphenyl ether, a dihalodiphenyl sulfone, a dihalodiphenyl sulfoxide, or a dihalodiphenyl ketone. The dihaloaromatic compound may be used either alone or in any combination thereof. Specific exemplary dihaloaromatic compounds include, without limitation, p-dichlorobenzene; m-dichlorobenzene; o-dichlorobenzene; 2,5-dichlorotoluene; 1,4-dibromobenzene; 1,4-dichloronaphthalene; 1-methoxy-2,5-dichlorobenzene; 4,4'-dichlorobiphenyl; 3,5-dichlorobenzoic acid; 4,4'-dichlorodiphenyl ether; 4,4'-dichlorodiphenyl sulfone; 4,4'-dichlorodiphenyl sulfoxide; and 4,4'-dichlorodiphenyl ketone. The halogen atom may be fluorine, chlorine, bromine, or iodine, and the two halogen atoms in the same dihaloaromatic compound may be the same or different from each other. In one embodiment, o-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, or a mixture of two or more of these compounds is used as the dihaloaromatic compound. As is known in the art, monohalo compounds (not necessarily aromatic compounds) can also be used in combination with dihaloaromatic compounds to form end groups of polyarylene sulfides or to control the polymerization reaction and / or molecular weight of polyarylene sulfides.
[0053]
[0062] The polyarylene sulfide may be a homopolymer or a copolymer. For example, the selective combination of dihaloaromatic compounds can result in polyarylene sulfide copolymers containing two or more different units. For example, when p-dichlorobenzene is used in combination with m-dichlorobenzene or 4,4'-dichlorodiphenyl sulfone, the polyarylene sulfide copolymer has the formula:
[0054] [ka]
[0055] and a segment having the structure of the formula:
[0056] [ka]
[0057] or a segment having the structure of the formula:
[0058] [ka]
[0059] It is possible to form a polyarylene sulfide copolymer containing segments having the structure:
[0063] Polyarylene sulfides may be linear, semi-linear, branched, or crosslinked. Linear polyarylene sulfides typically contain 80 mol% or more of the repeat unit -(Ar-S)-. Such linear polymers may also contain small amounts of branched or crosslinked units, but the amount of branched or crosslinked units is typically less than about 1 mol% of the total monomer units of the polyarylene sulfide. Linear polyarylene sulfide polymers may be random or block copolymers containing the repeat units described above. Semi-linear polyarylene sulfides may also have a crosslinked or branched structure in which a small amount of one or more monomers having three or more reactive functional groups are introduced into the polymer. As an example, the monomeric components used to form the semi-linear polyarylene sulfide may include a certain amount of polyhaloaromatic compounds having two or more halogen substituents per molecule, which can be used to prepare branched polymers. Such monomers are represented by the formula R'X nwhere each X is selected from chlorine, bromine, and iodine, n is an integer from 3 to 6, and R' is a polyvalent aromatic group of valence n that may have up to about four methyl substituents, and the total number of carbon atoms in R' is in the range of 6 to about 16. Examples of some polyhaloaromatic compounds substituted with more than two halogens per molecule that can be used to form semi-linear polyarylene sulfides include 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,3-dichloro-5-bromobenzene, 1,2,4-triiodobenzene, 1,2,3,5-tetrabromobenzene, hexachlorobenzene, 1,3,5-trichloro-2,4,6-trimethylbenzene, 2,2',4,4'-tetrachlorobiphenyl, 2,2',5,5'-tetra-iodobiphenyl, 2,2',6,6'-tetrabromo-3,3',5,5'-tetramethylbiphenyl, 1,2,3,4-tetrachloronaphthalene, 1,2,4-tribromo-6-methylnaphthalene, and the like, and mixtures thereof.
[0060]
[0064] Another example of a suitable semi-crystalline polymer is a polyamide. For example, the polyamide may be an aromatic polyamide in one embodiment. In this regard, the aromatic polyamide may have a relatively high melting temperature, for example, as determined using differential scanning calorimetry according to ISO Test No. 11357, of about 200°C or more, in some embodiments, about 220°C or more, and in some embodiments, about 240°C to about 320°C. The glass transition temperature of the aromatic polyamide is similarly generally about 110°C to about 160°C. In another embodiment, the aromatic polyamide may be an aliphatic polyamide. In this regard, the aliphatic polyamide may also have a relatively high melting temperature, for example, as determined using differential scanning calorimetry according to ISO Test No. 11357, of about 180°C or more, in some embodiments, about 200°C or more, and in some embodiments, about 210°C to about 320°C. The glass transition temperature of the aliphatic polyamide is similarly generally about 30°C to about 170°C.
[0061]
[0065] Aromatic polyamides typically contain repeat units held together by amide linkages (NH-CO) and are synthesized by polycondensation of dicarboxylic acids (e.g., aromatic dicarboxylic acids), diamines (e.g., aliphatic diamines), and the like. For example, aromatic polyamides may contain aromatic repeat units derived from aromatic dicarboxylic acids, such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,4-phenylenedioxy-diacetic acid, 1,3-phenylenedioxy-diacetic acid, diphenic acid, 4,4'-oxydibenzoic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and the like, and combinations thereof. Terephthalic acid is particularly suitable. Of course, it should be understood that other types of acid units, such as aliphatic dicarboxylic acid units, polyfunctional carboxylic acid units, and the like, may also be utilized.
[0062]
[0066] Aliphatic polyamides also typically contain repeat units held together by amide linkages (NH-CO). These polyamides may be synthesized by a variety of techniques. For example, polyamides may be formed by ring-opening polymerization, such as ring-opening polymerization of caprolactam. These polyamides may also be synthesized by polycondensation of dicarboxylic acids (e.g., aliphatic dicarboxylic acids), diamines, and the like. For example, aromatic polyamides may contain aliphatic repeat units derived from aliphatic dicarboxylic acids, such as adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, brassylic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, dimer acid, cis- and / or trans-cyclohexane-1,4-dicarboxylic acid, cis- and / or trans-cyclohexane-1,3-dicarboxylic acid, and combinations thereof. Adipic acid is particularly suitable.
[0063]
[0067] The polyamide may also contain aliphatic repeat units derived from aliphatic diamines typically having 4 to 14 carbon atoms. Examples of such diamines include linear aliphatic alkylenediamines such as 1,4-tetramethylenediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, etc.; branched aliphatic alkylenediamines such as 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 2-methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, etc.; and combinations thereof. Repeat units derived from 1,9-nonanediamine and / or 2-methyl-1,8-octanediamine are particularly preferred. Of course, other diamine units such as alicyclic diamines, aromatic diamines, etc. may also be utilized.
[0064]
[0068] Particularly preferred aromatic polyamides include poly(nonamethylene terephthalamide) (PA9T), poly(nonamethylene terephthalamide / nonamethylene decanediamide) (PA9T / 910), poly(nonamethylene terephthalamide / nonamethylene dodecanediamide) (PA9T / 912), poly(nonamethylene terephthalamide / 11-amino undecane amide) (PA9T / 11), poly(nonamethylene terephthalamide / 12-amino dodecane amide) (PA9T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 11), poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA12T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA12T / 12), poly(decamethylene terephthalamide / 12-amino do ... do) (PA10T / 12), poly(decamethylene terephthalamide / decamethylene dodecanediamide) (PA10T / 1010), poly(decamethylene terephthalamide / decamethylene dodecanediamide) (PA10T / 1012), poly(decamethylene terephthalamide / tetramethylene hexanediamide) (PA10T / 46), poly(decamethylene terephthalamide / caprolactam) (PA10T / 6), poly(decamethylene terephthalamide / hexamethylene hexanediamide) (PA10T / 66), poly(dodecamethylene terephthalamide / dodecamethylene dodecanediamide) (poly(dodecamethylene terephthalamide / hexamethylene hexanediamide) Poly(dodecamethylene terephthalamide / dodecamelhylene dodecanediarnide) (PA12T / 1212), poly(dodecamethylene terephthalamide / caprolactam) (PA12T / 6), poly(dodecamethylene terephthalamide / hexamethylene hexanediamide) (PA12T / 66), polyphthalamide (PPA), and the like. Particularly suitable aliphatic polyamides may include polyamide 4,6, polyamide 5,10, polyamide 6, polyamide 6,6, polyamide 6,9, polyamide 6,10, polyamide 6,12, polyamide 11, polyamide 12, and the like. Still other examples of suitable aromatic polyamides are described in U.S. Pat. No. 8,324,307 to Harder et al.
[0065]
[0069] Another suitable semi-crystalline aromatic polymer that may be utilized in the present invention is polyaryletherketone. Polyaryletherketone is a semi-crystalline polymer having a relatively high melting temperature, such as from about 300°C to about 400°C, in some embodiments from about 310°C to about 390°C, and in some embodiments from about 330°C to about 380°C. The glass transition temperature may be from about 110°C to about 200°C as well. Particularly suitable polyaryletherketones are those that contain primarily phenyl moieties in combination with ketone and / or ether moieties. Examples of such polymers include polyetheretherketone ("PEEK"), polyetherketone ("PEK"), polyetherketoneketone ("PEKK"), polyetherketoneetherketoneketone ("PEKEKK"), polyetheretherketoneketone ("PEEKK"), polyether-diphenyl-ether-ether-diphenyl-ether-phenyl-ketone-phenyl, and the like, as well as blends and copolymers thereof.
[0066]
[0070] In addition to the polymers mentioned above, crystalline polymers may also be utilized in the polymer composition. Particularly suitable are liquid crystal polymers with high crystallinity that allow for efficient filling of small spaces in a mold. Liquid crystal polymers are generally classified as "thermotropic" insofar as they have a rod-like structure and can exhibit crystalline behavior in their molten state (e.g., thermotropic nematic state). These polymers may also be generally referred to as polyesters. The polymers have relatively high melting temperatures, such as from about 250°C to about 400°C, in some embodiments from about 280°C to about 390°C, and in some embodiments from about 300°C to about 380°C. Such polymers may be formed from one or more types of repeat units as known in the art. Liquid crystal polymers may contain, for example, one or more aromatic ester repeat units, typically in an amount of from about 60 mol.% to about 99.9 mol.%, in some embodiments from about 70 mol.% to about 99.5 mol.%, and in some embodiments from about 80 mol.% to about 99 mol.% of the polymer. The aromatic ester repeat unit generally has the following formula (I):
[0067] [ka]
[0068] (In the formula, Ring B is a substituted or unsubstituted 6-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted 6-membered aryl group fused to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted 6-membered aryl group linked to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 4,4-biphenylene); Y 1 and Y 2 are independently O, C(O), NH, C(O)HN, or NHC(O). It can be expressed as:
[0069]
[0071] Typically, Y 1 and Y 2 At least one of the repeating units is C(O). Examples of such aromatic ester repeating units include aromatic dicarboxylic acid repeating units (Y in formula I). 1 and Y 2 is C(O)), an aromatic hydroxycarboxylic acid repeating unit (Y in formula I) 1 is O and Y 2 is C(O)), as well as various combinations thereof.
[0070]
[0072] For example, aromatic dicarboxylic acid repeat units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic dicarboxylic acids can include, for example, terephthalic acid ("TA"), isophthalic acid ("IA"), and 2,6-naphthalenedicarboxylic acid ("NDA"). When utilized, repeat units derived from aromatic dicarboxylic acids (e.g., IA, TA, and / or NDA) each typically comprise from about 1 mol.% to about 40 mol.%, in some embodiments from about 2 mol.% to about 30 mol.%, and in some embodiments, from about 5 mol.% to about 25 mol.% of the polymer.
[0071]
[0073] Also, aromatic hydroxycarboxylic acid repeat units derived from aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 4-hydroxy-4'-biphenylcarboxylic acid, 2-hydroxy-6-naphthoic acid, 2-hydroxy-5-naphthoic acid, 3-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid ("HBA") and 6-hydroxy-2-naphthoic acid (HNA). When utilized, repeat units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically comprise about 20 mol.% or more of the polymer, in some embodiments about 25 mol.% or more, in some embodiments about 30 mol.% or more, in some embodiments about 40 mol.% or more, in some embodiments about 50 mol.% or more, in some embodiments about 55 mol.% to 100 mol.%, and in some embodiments about 60 mol.% to about 95 mol.%.
[0072]
[0074] Other repeat units can also be utilized in the polymer. For example, in certain embodiments, repeat units derived from aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic diols can include, for example, hydroquinone ("HQ") and 4,4'-biphenol ("BP"). When utilized, repeat units derived from aromatic diols (e.g., HQ and / or BP) typically comprise from about 1 mol.% to about 50 mol.%, in some embodiments from about 1 mol. to about 40 mol.%, in some embodiments from about 2 mol.% to about 40 mol.%, in some embodiments from about 5 mol.% to about 35 mol.%, in some embodiments from about 5 mol.% to about 25 mol.% of the polymer. Repeat units such as those derived from aromatic amides (e.g., acetaminophen ("APAP")), and / or aromatic amines (e.g., 4-aminophenol ("AP"), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.) may also be utilized. When utilized, repeat units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol.% to about 20 mol.%, in some embodiments from about 0.5 mol.% to about 15 mol.%, and in some embodiments from about 1 mol.% to about 10 mol.% of the polymer. It should also be understood that various other monomeric repeat units may be incorporated into the polymer. For example, in certain embodiments, the polymer may contain one or more repeat units derived from non-aromatic monomers, such as aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, and the like.Of course, in other embodiments, the polymer may be "fully aromatic" in that it contains no repeat units derived from non-aromatic (eg, aliphatic or alicyclic) monomers.
[0073]
[0075] Although not necessarily required, the liquid crystal polymer may be a "high naphthenic" polymer, so long as it contains a relatively high content of repeat units derived from naphthenic hydroxycarboxylic acids and naphthenic dicarboxylic acids, such as naphthalene-2,6-dicarboxylic acid ("NDA"), 6-hydroxy-2-naphthoic acid ("HNA"), or combinations thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) may be about 10 mol.% or more of the polymer, in some embodiments about 12 mol.% or more, in some embodiments about 15 mol.% or more, in some embodiments about 18 mol.% or more, in some embodiments about 30 mol.% or more, in some embodiments about 40 mol.% or more, in some embodiments about 45 mol.% or more, in some embodiments about 50 mol.% or more, in some embodiments about 60 mol.% or more, in some embodiments about 62 mol.% or more, in some embodiments about 68 mol.% or more, in some embodiments about 70 mol.% or more, in some embodiments about 70 mol.% to about 80 mol.%. Without being limited by theory, it is believed that such "high naphthene" polymers can reduce the tendency of the polymer composition to absorb water, which can facilitate stabilization of the dielectric constant and dielectric loss tangent in the high frequency range. That is, such high naphthenic polymers typically have a water absorption of about 0.015% or less, in some embodiments about 0.01% or less, and in some embodiments about 0.0001% to about 0.008% after immersion in water for 24 hours according to ISO 62-1: 2008. The high naphthenic polymers may also have a moisture absorption of about 0.01% or less, in some embodiments about 0.008% or less, and in some embodiments about 0.0001% to about 0.006% after exposure to a humid atmosphere (relative humidity 50%) at a temperature of 23° C. according to ISO 62-4: 2008.
[0074]
[0076] In one embodiment, for example, the repeat unit derived from HNA may constitute 30 mol.% or more of the polymer, in some embodiments, about 40 mol.% or more, in some embodiments, about 45 mol.% or more, in some embodiments, 50 mol.% or more, in some embodiments, about 60 mol.% or more, in some embodiments, about 62 mol.% or more, in some embodiments, about 68 mol.% or more, in some embodiments, about 70 mol.% or more, in some embodiments, about 70 mol.% to about 80 mol.%. The liquid crystal polymer may also contain various other monomers. For example, the polymer may contain about 10 mol.% to about 40 mol.%, in some embodiments, about 15 mol.% to about 35 mol.%, and in some embodiments, about 20 mol.% to about 30 mol.% of the repeat unit derived from HBA. When utilized, the molar ratio of HNA to HBA may be selectively controlled within a particular range to facilitate achievement of desired properties, for example, from about 0.1 to about 40, in some embodiments from about 0.5 to about 20, in some embodiments from about 0.8 to about 10, and in some embodiments from about 1 to about 5. The polymer may also contain aromatic dicarboxylic acids (e.g., IA and / or TA) in an amount of from about 1 mol.% to about 40 mol.%, in some embodiments from about 5 mol.% to about 25 mol.%, and / or aromatic diols (e.g., BP and / or HQ) in an amount of from about 1 mol.% to about 40 mol.%, in some embodiments from about 5 mol.% to about 25 mol.%. However, in some cases, it may be desirable to minimize the presence of such monomers in the polymer to facilitate achievement of desired properties. For example, the total amount of aromatic dicarboxylic acids (e.g., IA and / or TA) may be about 20 mol.% or less, in some embodiments about 15 mol.% or less, in some embodiments about 10 mol.% or less, in some embodiments, 0 mol.% to about 5 mol.%, and in some embodiments, 0 mol.% to about 2 mol.% of the polymer.Similarly, the total amount of aromatic dicarboxylic acids (e.g., IA and / or TA) may be about 20 mol.% or less of the polymer, in some embodiments about 15 mol.% or less, in some embodiments about 10 mol.% or less, in some embodiments, 0 mol.% to about 5 mol.%, and in some embodiments, 0 mol.% to about 2 mol.% (e.g., 0 mol.%).
[0075]
[0077] In another embodiment, the repeat unit derived from NDA may constitute 10 mol.% or more of the polymer, in some embodiments, about 12 mol.% or more, in some embodiments, about 15 mol.% or more, and in some embodiments, about 18 mol.% to about 95 mol.%. In such an embodiment, the liquid crystal polymer may further contain various other monomers, such as aromatic hydroxycarboxylic acid (e.g., HBA) in an amount of about 20 mol.% to about 60 mol.%, in some embodiments, about 30 mol.% to about 50 mol.%, aromatic dicarboxylic acid (e.g., IA and / or TA) in an amount of about 2 mol.% to about 30 mol.%, in some embodiments, about 5 mol.% to about 25 mol.%, and / or aromatic diol (e.g., BP and / or HQ) in an amount of about 2 mol.% to about 40 mol.%, in some embodiments, about 5 mol.% to about 35 mol.%.
[0076]
[0078] Additionally, although not required, the liquid crystal polymer may be a "low naphthene" polymer so long as it contains a minimal amount of repeat units derived from naphthenic hydroxycarboxylic acids and naphthenic dicarboxylic acids, such as naphthalene-2,6-dicarboxylic acid ("NDA"), 6-hydroxy-2-naphthoic acid ("HNA"), or combinations thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or combinations of HNA and NDA) is typically 10 mol.% or less of the polymer, in some embodiments about 15 mol.% or less, in some embodiments about 8 mol.% or less, in some embodiments about 6 mol.% or less, and in some embodiments 1 mol.% to about 5 mol.% (e.g., 0 mol.%). In one particular embodiment, the liquid crystal polymer may be formed from repeat units derived from 4-hydroxybenzoic acid ("HBA"), and terephthalic acid ("TA") and / or isophthalic acid ("IA"), as well as various other optional components. Repeat units derived from 4-hydroxybenzoic acid ("HBA") may comprise from about 10 mol.% to about 80 mol.%, in some embodiments from about 30 mol.% to about 75 mol.%, and in some embodiments from about 45 mol.% to about 70% of the polymer. Similarly, repeat units derived from terephthalic acid ("TA") and / or isophthalic acid ("IA") may comprise from about 5 mol.% to about 40 mol.%, in some embodiments from about 10 mol.% to about 35 mol.%, and in some embodiments from about 15 mol.% to about 35% of the polymer. Also, repeat units derived from 4,4'-biphenol ("BP") and / or hydroquinone ("HQ") may be utilized in an amount of from about 1 mol.% to about 30 mol.%, in some embodiments from about 2 mol.% to about 25 mol.%, and in some embodiments from about 5 mol.% to about 20 mol.% of the polymer. Other possible repeating units can include those derived from 6-hydroxy-2-naphthoic acid ("HNA"), 2,6-naphthalenedicarboxylic acid ("NDA"), and / or acetaminophen ("APAP").For example, in certain embodiments, repeat units derived from HNA, NDA and / or APAP, when utilized, may each constitute from about 1 mol.% to about 35 mol.%, in some embodiments from about 2 mol.% to about 30 mol.%, and in some embodiments, from about 3 mol.% to about 25 mol.%.
[0077]
[0079] In certain embodiments, all of the liquid crystal polymers utilized in the polymer composition are "high naphthene" polymers such as those described above. However, in other embodiments, "low naphthene" liquid crystal polymers may be utilized in the composition, in which the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is less than 10 mol.% of the polymer, in some embodiments about 8 mol.% or less, in some embodiments about 6 mol.% or less, and in some embodiments about 1 mol.% to about 5 mol.%. When utilized, it is generally desirable that such low naphthene polymers are present only in relatively low amounts. For example, when utilized, the low naphthene liquid crystalline polymer typically comprises from about 1 wt.% to about 50 wt.%, in some embodiments from about 2 wt.% to about 40 wt.%, in some embodiments from about 5 wt.% to about 30 wt.%, of the total amount of liquid crystalline polymer in the composition, and from about 0.5 wt.% to about 45 wt.%, in some embodiments from about 2 wt.% to about 35 wt.%, and in some embodiments from about 5 wt.% to about 25 wt.% of the total composition. In contrast, the high naphthene liquid crystalline polymer typically comprises from about 50 wt.% to about 99 wt.%, in some embodiments from about 60 wt.% to about 98 wt.%, and in some embodiments from about 70 wt.% to about 95 wt.%, of the total amount of liquid crystalline polymer in the composition, and from about 55 wt.% to about 99.5 wt.%, in some embodiments from about 65 wt.% to about 98 wt.%, and in some embodiments from about 75 wt.% to about 95 wt.% of the total composition.
[0078]
[0080] The polymer in the polymer matrix may be present in an amount of about 30 wt.% or more, in some embodiments about 40 wt.% or more, in some embodiments about 40 wt.% to about 99.5 wt.%, in some embodiments about 50 wt.% to about 95 wt.%, in some embodiments about 60 wt.% to about 90 wt.%, and in some embodiments about 60 wt.% to about 85 wt.% of the polymer composition.
[0079] B. Laser Activatable Additives
[0081] The polymer composition may be "laser activatable" in the sense that it contains an additive that can be activated by a laser direct structuring ("LDS") process. In such a process, the additive is exposed to a laser that causes the liberation of metal. The laser thereby patterns the conductive elements in the part, leaving behind a roughened surface containing embedded metal particles. These particles act as nuclei for crystal growth during a subsequent plating process (e.g., copper plating, gold plating, nickel plating, silver plating, zinc plating, tin plating, etc.).
[0080]
[0082] The laser activatable additive generally comprises a spinel crystal, which may comprise two or more metal oxide cluster configurations within a definable crystal formation. For example, all crystal formations may have the following general formula: A.B. 2 O 4 (In the formula, A is a metal cation having a valence of two, such as cadmium, chromium, manganese, nickel, zinc, copper, cobalt, iron, magnesium, tin, titanium, and the like, and combinations thereof; B is a metal cation having a valence of 3, such as chromium, iron, aluminum, nickel, manganese, tin, and combinations thereof. may have the following structure:
[0081]
[0083] Generally, A in the above formula provides the main cation component of the first metal oxide cluster, and B provides the main cation component of the second metal oxide cluster. These oxide clusters may have the same or different structures. For example, in one embodiment, the first metal oxide cluster has a tetrahedral structure and the second metal oxide cluster has an octahedral cluster. Nevertheless, the clusters can be combined to provide a single identifiable crystal type structure with increased sensitivity to electromagnetic radiation. Examples of suitable spinel crystals include, for example, MgAl 2 O 4 , ZnAl 2 O 4 , FeAl 2 O 4 , CuFe 2 O 4 , CuCr 2 O 4 , MnFe 2 O 4 , NiFe 2 O 4 , TiFe 2 O 4 , FeCr 2 O 4 , MgCr 2 O 4 Copper chromium oxide (CuCr 2 O 4 ) is particularly suitable for use in the present invention and is available from Shepherd Color Co. under the designation "Shepherd Black 1GM."
[0082]
[0084] The laser activatable additive may comprise from about 0.1 wt.% to about 30 wt.%, in some embodiments from about 0.5 wt.% to about 20 wt.%, and in some embodiments, from about 1 wt.% to about 10 wt.% of the polymer composition.
[0083] C. Dielectric Materials
[0085] To aid in achieving desired dielectric properties, the polymeric composition may also contain a dielectric material. The dielectric material is typically utilized in an amount of about 10 wt.% to about 70 wt.%, in some embodiments about 20 wt.% to about 60 wt.%, and in some embodiments about 30 wt.% to about 50 wt.% of the composition. In certain embodiments, it may be desirable to selectively control the volume resistivity of the dielectric material such that the dielectric material is generally semiconductive in nature. For example, the dielectric material may have a volume resistivity of about 0.1 ohm·cm to about 1×10, e.g., as determined at a temperature of about 20° C. according to ASTM D257-14. 12 ohm cm, in some embodiments from about 0.5 ohm cm to about 1 x 10 11 ohm cm, in some embodiments, from about 1 to about 1 x 10 10 ohm cm, in some embodiments, from about 2 to about 1 x 10 8 It may have a volume resistivity in ohms·cm. This may be achieved by selecting a single material with the desired volume resistivity, or by blending multiple materials together (e.g., insulating and conductive) such that the resulting blend has the desired volume resistivity.
[0084]
[0086] In one embodiment, for example, inorganic oxide materials may be utilized that may exhibit a linear response of charge (or polarization) versus voltage. These materials may exhibit a total reversible polarization of charge within the crystal structure after an applied electric field is removed. Suitable inorganic oxide materials for this purpose may include, for example, ferroelectric and / or paraelectric materials. Examples of suitable ferroelectric materials include, for example, barium titanate (BaTiO 3 ), strontium titanate (SrTiO 3 ), calcium titanate (CaTiO 3 ), magnesium titanate (MgTiO 3 ), strontium barium titanate (SrBaTiO 3 ), Sodium Barium Niobate (NaBa 2 Nb 5 O 15 ), potassium barium niobate (KBa 2 Nb 5 O 15), calcium zirconate (CaZrO 3 ), titanite (CaTiSiO 5 ), and combinations thereof. Further suitable paraelectric materials include, for example, titanium dioxide (TiO 2 ), Tantalum Pentoxide (Ta 2 O 5 ), hafnium dioxide (HfO 2 ), niobium pentoxide (Nb 2 O 5 ), Alumina (Al 2 O 3 ), zinc oxide (ZnO), and the like, and combinations thereof. Particularly suitable inorganic oxide materials include TiO 2 , BaTiO 3 , SrTiO 3 , CaTiO 3 , MgTiO 3 , BaSrTi 2 O 6 and ZnO. Of course, other types of inorganic oxide materials (e.g., mica) can be used as the dielectric material. Carbon materials such as graphite, carbon black, etc. can be used as well.
[0085]
[0087] The shape and size of the dielectric material are not particularly limited and may include particles, fine powders, fibers, whiskers, tetrapods, plates, and the like. For example, in one embodiment, the dielectric material may include particles having an average diameter of about 0.01 to about 100 micrometers, and in some embodiments, about 0.10 to about 20 micrometers. In another embodiment, the dielectric material may include fibers and / or whiskers having an average diameter of about 0.1 to about 35 micrometers, and in some embodiments, about 0.2 to about 20 micrometers, and in some embodiments, about 0.5 to about 15 micrometers. When utilized, the whiskers may have an aspect ratio of about 1 to about 100, and in some embodiments, about 2 to about 80, and in some embodiments, about 4 to about 50. The volume average length of such whiskers may range, for example, from about 1 to about 200 micrometers, and in some embodiments, from about 2 to about 150 micrometers, and in some embodiments, from about 5 to about 100 micrometers.
[0086]
[0088] As indicated above, various techniques may be utilized to facilitate achieving the desired volume resistivity. For example, in one embodiment, inorganic oxide materials may be utilized having a volume resistivity of 0.1 ohm·cm to about 500 ohm·cm, in some embodiments, about 0.5 ohm·cm to about 250 ohm·cm, in some embodiments, about 1 to about 100 ohm·cm, and in some embodiments, about 2 to about 50 ohm·cm, as determined, for example, at a temperature of about 20° C. according to ASTM D257-14. One example of such a material is an inorganic oxide whisker having a three-dimensional structure (e.g., zinc oxide whisker). For example, the inorganic oxide whisker may have a central body and multiple needle-like crystals extending radially therefrom to form a three-dimensional structure. When such whiskers are incorporated into a resin, the needle-like crystals may be placed in close proximity to one another, thereby increasing the likelihood of forming a stable conductive path. The number of needle-like crystals may vary, for example, about 2 or more, in some embodiments, 3 to 8, and in some embodiments, 4 to 6 (e.g., 4). For example, if four needle-shaped crystals are present, the whiskers have a "tetrapod" morphology even though one or more of those needle-shaped crystal protrusions may break during processing and / or manufacturing. The central body and / or base portion of the needle-shaped crystals may have an average diameter within the ranges described above, for example, about 0.1 to about 35 micrometers, in some embodiments, about 0.2 to about 20 micrometers, and in some embodiments, about 0.5 to about 15 micrometers. The volume average length (base to tip) of the needle-shaped crystals may also have a volume average length within the ranges described above, for example, about 1 to about 200 micrometers, in some embodiments, about 2 to about 150 micrometers, and in some embodiments, about 5 to about 100 micrometers. Such whiskers may be formed by heat treating a metal powder (e.g., zinc) having an oxide film on its surface in an atmosphere containing molecular oxygen, as described, for example, in U.S. Patent No. 4,960,654 to Yoshinaka et al. One particularly suitable type of whisker having such characteristics includes single crystal tetrapod zinc oxide whiskers available from Panasonic under the trade name Pana-Tetra™.
[0087]
[0089] In another embodiment, the solubility of about 1×10 3 ~Approx. 1×10 12 ohm cm, in some embodiments, approximately 1×10 4 ~Approx. 1×10 11 ohm cm, in some embodiments, approximately 1×10 5 ~Approx. 1×10 10 ohm cm, in some embodiments, approximately 1×10 6 ~Approx. 1×10 8 Carbon materials having a volume resistivity of ohms·cm may be utilized. For example, carbon materials (e.g., particles, fibers, etc.) having a volume resistivity within the above range may be obtained by calcining an organic material (e.g., petroleum tar, petroleum pitch, coal tar or coal pitch) at high temperatures (e.g., 400°-900° C.) in an inert atmosphere, as described, for example, in U.S. Patent No. 8,642,682 to Nishihata et al. The resulting carbon materials typically have a high carbon content, such as about 80 wt.% or more, in some embodiments about 85 wt.% or more, and in some embodiments about 90 wt.% to about 98 wt.%. One particularly suitable type of carbon material having such characteristics is available from Kureha Extron under the trade name Krefine™.
[0088]
[0090] Of course, as discussed above, conductive materials may be utilized in combination with insulating materials to help achieve a desired volume resistivity. Conductive materials generally have a resistivity of less than about 0.1 ohm-cm, and in some embodiments, less than about 1×10 -8 ~Approx. 1×10 -2 Insulating materials have a volume resistivity of about 1 x 10 Ohm cm. 12 Greater than ohm-cm, in some embodiments approximately 1×10 13 ~Approx. 1×10 18The conductive material has a volume resistivity of ohm·cm. Suitable conductive materials include, for example, conductive carbon materials (e.g., graphite, carbon black, fibers, graphene, nanotubes, etc.), metals, etc. Similarly, suitable insulating materials include the inorganic oxide materials (e.g., particles) mentioned above, such as titanium dioxide (TiO 2 When utilized, the ratio of the weight percentage of the insulating material in the polymer composition to the weight percentage of the conductive material in the composition may be from about 3 to about 20, in some embodiments from about 7 to about 18, and in some embodiments from about 8 to about 15. For example, the conductive material may comprise from about 1 wt.% to about 20 wt.%, in some embodiments from about 3 wt.% to about 18 wt.%, and in some embodiments from about 5 wt.% to about 15 wt.% of the dielectric material, while the insulating material may comprise from about 80 wt.% to about 99 wt.%, in some embodiments from about 82 wt.% to about 97 wt.%, and in some embodiments from about 85 wt.% to about 95 wt.% of the dielectric material. Similarly, the conductive material may comprise from about 0.1 wt.% to about 15 wt.%, in some embodiments from about 0.5 wt.% to about 12 wt.%, and in some embodiments, from about 1 wt.% to about 10 wt.%, of the polymer composition, while the insulating material may comprise from about 20 wt.% to about 60 wt.%, in some embodiments, from 25 wt.% to about 55 wt.%, and in some embodiments, from about 30 wt.% to about 50 wt.% of the polymer composition.
[0089] D. Fibrous fillers
[0091] Fibrous fillers may also be utilized in the polymeric compositions to improve the thermal and mechanical properties of the polymeric compositions without significantly affecting electrical performance. Unlike the hollow inorganic fillers described above, these fibrous fillers may be non-hollow (or solid) fibrous fillers. Fibrous fillers typically include fillers that have a high degree of tensile strength relative to their mass. For example, the ultimate tensile strength of the fibers (determined according to ASTM D2101) is typically about 1,000 to about 15,000 megapascals ("MPa"), in some embodiments about 2,000 MPa to about 10,000 MPa, and in some embodiments about 3,000 MPa to about 6,000 MPa. To help maintain desired dielectric properties, such high strength fibers may be formed from materials that are generally insulating in nature, such as glass, ceramic or mineral (e.g., alumina or silica), aramid (e.g., Kevlar® sold by EI duPont de Nemours, Wilmington, Del.), minerals, polyolefins, polyesters, and the like.
[0090]
[0092] In one embodiment, the fibrous filler may include glass fibers, mineral fibers, or mixtures thereof. For example, in one embodiment, the fibrous filler may include glass fibers. Particularly suitable glass fibers may include E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, and the like. In another embodiment, the fibrous filler may include mineral fibers. Mineral fibers may include those derived from silicates, such as neosilicates, sorosilicates, inosilicates (e.g., calcium inosilicates such as wollastonite; calcium magnesium inosilicates such as tremolite; calcium magnesium iron inosilicates such as actinolite; magnesium iron inosilicates such as anthophillite, and the like), phyllosilicates (e.g., aluminum phyllosilicates such as palygorskite), tectosilicates, and the like; sulfates such as calcium sulfate (e.g., dehydrated or anhydrite); mineral wool (e.g., rock or slag wool), and the like. Particularly suitable are inosilicates such as wollastonite fiber available from Nyco Minerals under the trade name NYGLOS® (eg, NYGLOS® 4W or NYGLOS® 8).
[0091]
[0093] Furthermore, although the fibrous filler may have a variety of different sizes, fibers having a particular aspect ratio may promote improvement of the mechanical properties of the polymer composition. That is, fibrous fillers having an aspect ratio (average length divided by nominal diameter) of about 2 or more, in some embodiments about 4 or more, in some embodiments about 5 to about 50, and in some embodiments about 8 to about 40 may be particularly beneficial. Such fibrous fillers may have a weight average length of, for example, about 10 micrometers or more, in some embodiments about 25 micrometers or more, in some embodiments about 50 micrometers or more to about 800 micrometers or less, and in some embodiments about 60 micrometers to about 500 micrometers. Also, such fibrous fillers may have a volume average length of, for example, about 10 micrometers or more, in some embodiments about 25 micrometers or more, in some embodiments about 50 micrometers or more to about 800 micrometers or less, and in some embodiments about 60 micrometers to about 500 micrometers.
[0092]
[0094] The fibrous filler may similarly have a nominal diameter of about 5 micrometers or more, in some embodiments about 6 micrometers or more, in some embodiments about 8 micrometers to about 40 micrometers, and in some embodiments about 9 micrometers to about 20 micrometers. The relative amount of fibrous filler may also be selectively controlled to facilitate achieving the desired mechanical and thermal properties without adversely affecting other properties of the polymer composition, such as its flowability and dielectric properties. In this regard, the fibrous filler may have a relative dielectric constant of about 6 or less, in some embodiments about 5.5 or less, in some embodiments about 1.1 to about 5, and in some embodiments about 2 to about 4.8 at a frequency of 1 GHz.
[0093]
[0095] The fibrous filler may be in modified or unmodified form and may be sized or chemically treated, for example to improve adhesion to plastics. In some cases, glass fibers may be sized to protect them and smooth them, as well as improve adhesion between the fibers and the matrix material. If present, the sizing may include silanes, film formers, lubricants, wetting agents, adhesives, optionally antistatic agents and plasticizers, emulsifiers, and optionally further additives. In one particular embodiment, the sizing may include silanes. Particular examples of silanes are aminosilanes, such as 3-trimethoxysilylpropylamine, N-(2-aminoethyl)-3-aminopropyltrimethoxy-silane, N-(3-trimethoxysilanylpropyl)ethane-1,2-diamine, 3-(2-aminoethyl-amino)propyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]-1,2-ethane-diamine.
[0094]
[0096] The fibrous filler may comprise, for example, from about 1 wt.% to about 40 wt.%, in some embodiments from about 3 wt.% to about 30 wt.%, and in some embodiments, from about 5 wt.% to about 20 wt.% of the polymer composition.
[0095]
[0097] The relative amount of the fibrous filler may also be selectively controlled to help achieve the desired mechanical and thermal properties without adversely affecting other properties of the polymer composition, such as its flow and dielectric properties, etc. For example, the fibrous filler may be utilized in an amount sufficient such that the weight ratio of the fibrous filler to the combined amount of dielectric material and laser activatable material is from about 0.05 to about 1, in some embodiments from about 0.05 to about 0.5, in some embodiments from about 0.06 to about 0.4, and in some embodiments from about 0.1 to about 0.3.
[0096] E. Hydrophobic Materials
[0098] If desired, an optional hydrophobic material distributed throughout the polymer matrix can also be utilized in the polymer composition. Without being limited by theory, it is believed that the hydrophobic material may help reduce the tendency of the polymer composition to absorb water, thereby assisting in stabilizing the dielectric constant and dissipation factor in the high frequency range. The weight ratio of polymer to hydrophobic material is typically from about 1 to about 20, in some embodiments from about 2 to about 15, and in some embodiments from about 3 to about 10. For example, the hydrophobic material may comprise from about 1 wt.% to about 60 wt.%, in some embodiments from about 2 wt.% to about 50 wt.%, and in some embodiments from about 5 wt.% to about 40 wt.% of the total polymer composition.
[0097]
[0099] Particularly suitable hydrophobic materials are low surface energy elastomers such as fluoropolymers, silicone polymers, etc. Fluoropolymers may contain, for example, a hydrocarbon backbone polymer in which some or all of the hydrogen atoms are replaced with fluorine atoms. The backbone polymer may be polyolefin-based and formed from unsaturated olefin monomers substituted with fluorine. The fluoropolymer may be a homopolymer of such fluorine-substituted monomers or a copolymer of fluorine-substituted monomers, or a mixture of fluorine-substituted and non-fluorine-substituted monomers. Along with fluorine atoms, the fluoropolymer may be substituted with other halogen atoms such as chlorine and bromine atoms. Representative monomers suitable for forming the fluoropolymers used in the present invention are tetrafluoroethylene ("TFE"), vinylidene fluoride ("VF2"), hexafluoropropylene ("HFP"), chlorotrifluoroethylene ("CTFE"), perfluoroethyl vinyl ether ("PEVE"), perfluoromethyl vinyl ether ("PMVE"), perfluoropropyl vinyl ether ("PPVE"), etc., and mixtures thereof. Specific examples of suitable fluoropolymers include polytetrafluoroethylene ("PTFE"), perfluoroalkyl vinyl ether ("PVE"), poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ether) ("PFA"), fluorinated ethylene propylene copolymer ("FEP"), ethylene tetrafluoroethylene copolymer ("ETFE"), polyvinylidene fluoride ("PVDF"), polychlorotrifluoroethylene ("PCTFE"), and TFE copolymers with VF2 and / or HFP, and mixtures thereof.
[0098]
[0100] In certain embodiments, the hydrophobic material (e.g., fluoropolymer) may have a particle size that is selectively controlled to promote the formation of a relatively low thickness film. For example, the hydrophobic material may have a median particle size (e.g., diameter) of about 1 to about 60 micrometers, in some embodiments about 2 to about 55 micrometers, in some embodiments about 3 to about 50 micrometers, and in some embodiments about 25 to about 50 micrometers, as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer), for example, according to ISO-13320:2009. The hydrophobic material may also have a narrow size distribution. That is, at least about 70% by volume of the particles, in some embodiments at least about 80% by volume of the particles, and in some embodiments at least about 90% by volume of the particles may have a size within the ranges mentioned above.
[0099] F. Particulate matter fillers
[0101] If desired, particulate fillers may be utilized to improve certain properties of the polymeric composition. The particulate fillers may be utilized in the polymeric composition in an amount of about 5 to about 60 parts by weight, in some embodiments about 10 to about 50 parts by weight, and in some embodiments about 15 to about 40 parts by weight per 100 parts of liquid crystal polymer utilized in the polymeric composition. For example, the particulate fillers may comprise about 5 wt.% to about 50 wt.%, in some embodiments about 10 wt.% to about 40 wt.%, and in some embodiments about 15 wt.% to about 30 wt.% of the polymeric composition.
[0100]
[0102] In certain embodiments, particles having a particular hardness value may be utilized to aid in improving the surface properties of the composition. For example, the hardness value may be about 2 or greater, in some embodiments about 2.5 or greater, in some embodiments about 3 to about 11, in some embodiments about 3.5 to about 11, and in some embodiments about 4.5 to about 6.5 on the Mohs hardness scale. Examples of such particles include, for example, silica (Mohs hardness 7), mica (Mohs hardness about 3); calcium carbonate (CaCO 3 , Mohs hardness 3.0), or copper hydroxide carbonate (Cu 2 CO 3(OH) 2 , Mohs hardness 4.0); 2 Fluorides such as calcium pyrophosphate (Ca 2 P 2 O 7 , Mohs hardness 5.0), anhydrous dicalcium phosphate (CaHPO 4 3.5 on the Mohs scale, or hydrated aluminum phosphate (AlPO 4 2H 2 O; Mohs hardness 4.5); phosphates such as calcium borosilicate hydroxide (Ca 2 B 5 SiO 9 (OH) 5 , Mohs hardness 3.5); alumina (AlO 2 , Mohs hardness 10.0); calcium sulfate (CaSO 4 , Mohs hardness 3.5), or barium sulfate (BaSO 4 , sulfates having a Mohs hardness of 3 to 3.5, and combinations thereof.
[0101]
[0103] The shape of the particles may vary as desired. For example, certain embodiments may utilize flake-shaped particles having a relatively high aspect ratio (e.g., average diameter divided by average thickness), such as about 10:1 or more, in some embodiments about 20:1 or more, and in some embodiments, about 40:1 to about 200:1. The average diameter of the particles may range from about 5 micrometers to about 200 micrometers, in some embodiments about 30 micrometers to about 150 micrometers, and in some embodiments about 50 micrometers to about 120 micrometers, as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer), for example, according to ISO 13320:2009. Suitable flake-shaped particles may be formed from natural and / or synthetic silicate minerals, such as mica, halloysite, kaolinite, illite, montmorillonite, vermiculite, palygorskite, pyrophyllite, calcium silicate, aluminum silicate, wollastonite, and the like. For example, mica is particularly suitable. For example, muscovite (KAl2 (AlSi 3 )O 10 (OH) 2 ), biotite (K(Mg,Fe) 3 (AlSi 3 )O 10 (OH) 2 ), phlogopite (KMg 3 (AlSi 3 )O 10 (OH) 2 ), red mica (K(Li,Al) 2-3 (AlSi 3 )O 10 (OH) 2 ), glauconite (K,Na)(Al,Mg,Fe) 2 (Si,Al) 4 O 10 (OH) 2 Mica in any form may generally be utilized, including, for example, talc, barium sulfate, calcium sulfate, calcium carbonate, and the like. Granular particles may also be utilized. Typically, such particles have an average diameter of about 0.1 to about 10 micrometers, in some embodiments about 0.2 to about 4 micrometers, and in some embodiments about 0.5 to about 2 micrometers, as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer), for example, according to ISO 13320:2009. Particularly suitable granular fillers may include, for example, talc, barium sulfate, calcium sulfate, calcium carbonate, and the like.
[0102]
[0104] The particulate filler may be formed primarily or entirely of one type of particle, such as flake-shaped particles (e.g., mica) or granular particles (e.g., barium sulfate). That is, such flake-shaped or granular particles may comprise about 50 wt.% or more of the particulate filler, and in some embodiments, about 75 wt.% or more (e.g., 100 wt.%). Of course, in other embodiments, flake-shaped and granular particles may be utilized in combination. In such embodiments, for example, the flake-shaped particles may comprise about 0.5 wt.% to about 20 wt.%, and in some embodiments, about 1 wt.% to about 10 wt.%, of the particulate filler, while the granular particles may comprise about 80 wt.% to about 99.5 wt.%, and in some embodiments, about 90 wt.% to about 99 wt.% of the particulate filler.
[0103]
[0105] If desired, the particles may also be coated with a fluorinated additive to aid in improving the processing of the composition, for example by providing better mold filling, internal lubrication, mold release, etc. The fluorinated additive may include a fluoropolymer containing a hydrocarbon backbone polymer in which some or all of the hydrogen atoms are replaced with fluorine atoms. The backbone polymer may be polyolefin-based and formed from an unsaturated olefin monomer substituted with fluorine. The fluoropolymer may be a homopolymer of such a fluorine-substituted monomer or a copolymer of a fluorine-substituted monomer, or a mixture of a fluorine-substituted monomer and a non-fluorine-substituted monomer. Along with the fluorine atoms, the fluoropolymer may be substituted with other halogen atoms, such as chlorine and bromine atoms. Representative monomers suitable for forming the fluoropolymers used in the present invention are tetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, chlorotrifluoroethylene, perfluoroethyl vinyl ether, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, etc., and mixtures thereof. Specific examples of suitable fluoropolymers include polytetrafluoroethylene, perfluoroalkyl vinyl ethers, poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ethers), fluorinated ethylene propylene copolymers, ethylene tetrafluoroethylene copolymers, polyvinylidene fluoride, polychlorotrifluoroethylene, and the like, and mixtures thereof.
[0104] G. Other Additives
[0106] A wide variety of additional additives may be included in the polymer composition, such as hollow fillers, lubricants, thermally conductive fillers, pigments, antioxidants, stabilizers, surfactants, waxes, flame retardants, anti-sag additives, nucleating agents (e.g., boron nitride), flow modifiers (e.g., alumina trihydrate), coupling agents, antimicrobial agents, pigments or other colorants, impact modifiers, and other materials added to improve properties and processability. Such optional materials may be utilized in the polymer composition in conventional amounts and in accordance with conventional processing techniques. When utilized, for example, lubricants and / or flow modifiers may comprise from about 0.05 wt.% to about 5 wt.%, and in some embodiments, from about 0.1 wt.% to about 1 wt.%, of the polymer composition.
[0105]
[0107] Although by no means required, the polymer composition may also include one or more hollow inorganic fillers to aid in achieving a desired dielectric constant. For example, such fillers may have a dielectric constant at 100 MHz of about 3.0 or less, in some embodiments about 2.5 or less, in some embodiments about 1.1 to about 2.3, and in some embodiments about 1.2 to about 2.0. Hollow inorganic fillers typically have an internal hollow space or cavity and may be synthesized using techniques known in the art. Hollow inorganic fillers may be made from conventional materials. For example, hollow inorganic fillers may include alumina, silica, zirconia, magnesia, glass, fly ash, borates, phosphates, ceramics, and the like. In one embodiment, hollow inorganic fillers may include hollow glass fillers, hollow ceramic fillers, and mixtures thereof. In one embodiment, the hollow inorganic fillers include hollow glass fillers. The hollow glass filler may be made from soda lime borosilicate glass, soda lime glass, borosilicate glass, sodium borosilicate glass, sodium silicate glass, or aluminosilicate glass. In this regard, in one embodiment, the composition of the glass is, but is not limited to, at least about 65 wt. % SiO 2 , 3 to 15% by weight of Na 2 O, 8-15% by weight CaO, 0.1-5% by weight MgO, 0.01-3% by weight Al 2 O 3, 0.01 to 1% by weight of K 2 O, and optionally other oxides (e.g., Li 2 O, Fe 2 O 3 , TiO 2 , B 2 O 3 In another embodiment, the composition may be about 50-58 wt.% SiO 2 , 25-30% by weight of Al 2 O 3 , 6-10% by weight CaO, 1-4% by weight Na 2 OK 2 0, and 1 to 5 weight percent of other oxides. Additionally, in one embodiment, the hollow glass filler may include more alkaline earth metal oxides than alkali metal oxides. For example, the weight ratio of alkaline earth metal oxides to alkali metal oxides may be greater than 1, in some embodiments greater than about 1.1, in some embodiments from about 1.2 to about 4, and in some embodiments from about 1.5 to about 3. Notwithstanding the above, it should be understood that the composition of the glass may vary depending on the type of glass utilized and still provide the benefits desired by the present invention.
[0106]
[0108] The hollow inorganic filler may have at least one dimension having an average value of about 1 micrometer or more, in some embodiments about 5 micrometers or more, in some embodiments about 8 micrometers or more, in some embodiments about 1 micrometer to about 150 micrometers, in some embodiments about 10 micrometers to about 150 micrometers, and in some embodiments about 12 micrometers to about 50 micrometers. In one embodiment, such average value is d 50 Further, the hollow inorganic filler may have a D value of about 3 micrometers or more, in some embodiments about 4 micrometers or more, in some embodiments from about 5 micrometers to about 20 micrometers, and in some embodiments from about 6 micrometers to about 15 micrometers. 10The hollow inorganic filler may have a D of about 10 micrometers or more, in some embodiments about 15 micrometers or more, in some embodiments from about 20 micrometers to about 150 micrometers, and in some embodiments, from about 22 micrometers to about 50 micrometers. 90 In this regard, the hollow inorganic filler may be present in a size distribution that may be Gaussian, normal or non-normal. In one embodiment, the hollow inorganic filler may have a Gaussian size distribution. In another embodiment, the hollow inorganic filler may have a normal size distribution. In a further embodiment, the hollow inorganic filler may have a non-normal size distribution. Examples of non-normal size distributions may include unimodal and multimodal (e.g., bimodal) size distributions. When referring to the above dimensions, such dimensions may be any dimension. However, in one embodiment, such dimensions refer to diameters. For example, such values for dimensions refer to the average diameter of a sphere. Dimensions such as average diameters may be determined according to 3M QCM 193.0. In this regard, in one embodiment, the hollow inorganic filler may refer to hollow spheres, such as hollow glass spheres. For example, the hollow inorganic filler may have an average aspect ratio of approximately 1. Generally, the average aspect ratio may be greater than or equal to about 0.8, and in some embodiments greater than or equal to about 0.85, and in some embodiments, from about 0.9 to about 1.3, and in some embodiments, from about 0.95 to about 1.05.
[0107]
[0109] In addition, the hollow inorganic filler may have a relatively thin wall to aid in the dielectric properties and weight reduction of the polymer composition. The wall thickness may be about 50% or less, in some embodiments about 40% or less, in some embodiments about 1% to about 30%, and in some embodiments about 2% to about 25% of the average dimension, e.g., average diameter, of the hollow inorganic filler. In addition, the hollow inorganic filler may have a particular true density that allows for easy handling and can provide a polymer composition with reduced weight. Generally, true density refers to the quotient obtained by dividing the mass of a hollow filler sample by the true volume of the mass of the hollow filler, where the true volume is referred to as the total volume of the hollow filler. In this regard, the true density of the hollow inorganic filler is about 0.1 g / cm 3 or more, in some embodiments, about 0.2 g / cm 3 or more, in some embodiments, about 0.3 g / cm 3 More than ~ approx. 1.2g / cm 3 , in some embodiments, about 0.4 g / cm 3 More than ~ approx. 0.9g / cm 3 True density may be determined according to 3M QCM 14.24.1.
[0108]
[0110] Even if the fillers are bubs, they may have mechanical strength that allows them to maintain their structural integrity, such that the fillers are less likely to break during processing and / or use. In this regard, the isotactic crush resistance of hollow inorganic fillers (i.e., at least 80 vol.%, e.g., at least 90 vol.%, of the hollow fillers survive) may be about 20 MPa or more, in some embodiments about 100 MPa or more, in some embodiments about 150 MPa to about 500 MPa, and in some embodiments about 200 MPa to about 350 MPa. The isotactic crush resistance may be determined according to 3M QCM 14.1.8.
[0109]
[0111] The alkalinity of the hollow inorganic filler may be about 1.0 meq / g or less, in some embodiments about 0.9 meq / g or less, in some embodiments about 0.1 meq / g to about 0.8 meq / g, in some embodiments about 0.2 meq / g to about 0.7 meq / g. The alkalinity may be determined according to 3M QCM 55.19. To provide a relatively low alkalinity, the hollow inorganic filler may be treated with a suitable acid, such as phosphoric acid. Additionally, the hollow inorganic filler may also include a surface treatment to help provide better compatibility with other components in the polymer and / or polymer composition. By way of example, the surface treatment may be silanization. In particular, the surface treatment may include, but is not limited to, aminosilanes, epoxysilanes, and the like.
[0110]
[0112] If utilized, hollow inorganic fillers may comprise, for example, about 1 wt.% or more, in some embodiments about 4 wt.% or more, in some embodiments, about 5 wt.% to about 40 wt.%, and in some embodiments, about 10 wt.% to about 30 wt.% of the polymer composition.
[0111] II. Formation
[0113] The components used to form the polymer composition may be combined together using any of a variety of different techniques known in the art. For example, in one particular embodiment, the polymer, the laser activatable additive, and other optional additives are melt processed as a mixture in an extruder to form the polymer composition. The mixture may be melt kneaded at a temperature of about 250°C to about 450°C in a single or multiple screw extruder. In one embodiment, the mixture may be melt processed in an extruder that includes multiple temperature zones. The temperature of the individual zones is typically set to within about -60°C to about 25°C of the melting temperature of the polymer. By way of example, the mixture may be melt processed using a twin screw extruder, such as a Leistritz 18mm co-rotating fully intermeshing twin screw extruder. A general purpose screw design may be used to melt process the mixture. In one embodiment, the mixture containing all of the components may be fed by a metered feeder into the feed throat of the first barrel. In another embodiment, different components may be added at different addition points of the extruder, as is known. For example, the polymer can be applied to a feed port and certain additives (e.g., laser activatable additives and / or other additives) can be fed downstream at the same or different temperature zones. In either case, the resulting mixture can be melted, mixed, and then extruded through a die. The extruded polymer composition can then be quenched in a water bath to solidify, pelletized in a pelletizer, and then dried.
[0112]
[0114] The melt viscosity of the polymer composition is generally low enough to flow easily into a mold cavity to form a small sized circuit board. For example, in one particular embodiment, the polymer composition is melted at a temperature of 1,000 s. -1 In some embodiments, the melt viscosity is about 5 Pa·s or more, and in some embodiments about 10 Pa·s or more, and in some embodiments, about 10 Pa·s to about 500 Pa·s, in some embodiments, about 5 Pa·s to about 150 Pa·s, in some embodiments, about 5 Pa·s to about 100 Pa·s, in some embodiments, about 10 Pa·s to about 100 Pa·s, and in some embodiments, about 15 to about 90 Pa·s, as determined at a shear rate of 10 Pa·s.
[0113] III. Substrate
[0115] Once formed, the polymer composition can be molded into a substrate of the desired shape. Typically, the substrate is molded using a one-component injection molding process in which dried and preheated plastic granules are injected into a mold. These substrates can be used in antenna systems and can be bonded to antenna elements.
[0114]
[0116] As indicated above, a laser direct structuring process ("LDS") may then be used to form conductive elements on the substrate. Activation with a laser results in a physicochemical reaction that cracks the spinel crystal and liberates metal atoms. These metal atoms may act as nuclei for metallization (e.g., reductive copper coating). Additionally, the laser creates a microscopically irregular surface and abrades the polymer matrix to create numerous microscopic depressions and grooves in which copper can adhere during metallization.
[0115]
[0117] The invention may be better understood with reference to the following examples. EXAMPLES
[0116] Test Method
[0118] Melt viscosity: Melt viscosity (Pa s) was measured at a shear rate of 1,000 s using a Dynisco LCR7001 capillary rheometer. -1 and 15°C above the melt temperature (e.g., about 350°C) according to ISO Test No. 11443:2005. The rheometer orifice (die) had a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an entrance angle of 180°. The barrel diameter was 9.55 mm + 0.005 mm and the rod length was 233.4 mm.
[0117]
[0119] Melting temperature: Melting temperature ("Tm") may be determined by differential scanning calorimetry ("DSC") as known in the art. Melting temperature is the differential scanning calorimetry (DSC) peak melting temperature as determined by ISO test No. 11357-2:2013. Based on the DSC procedure, samples were heated and cooled at 20°C per minute using DSC measurements performed on a TA Q2000 instrument as described in ISO standard 10350.
[0118]
[0120] Deflection Temperature Under Load ("DTUL"): Deflection temperature under load may be determined according to ISO Test No. 75-2:2013 (technically equivalent to ASTM D648-07). More specifically, a test specimen sample of 80 mm length, 10 mm thickness, and 4 mm width may be subjected to an edgewise three-point bend test with a specified load (maximum external fiber stress) of 1.8 megapascals. The specimen is lowered into a silicone oil bath and the temperature is increased at 2°C per minute until the specimen deflects 0.25 mm (0.32 mm per ISO Test No. 75-2:2013).
[0119]
[0121] Tensile modulus, tensile stress and tensile elongation: Tensile properties may be tested according to ISO Test No. 527:2012 (technically equivalent to ASTM D638-14). Modulus and strength measurements may be performed on the same test specimen sample of 80 mm length, 10 mm thickness, and 4 mm width. The test temperature may be about 23°C, and the test speed may be 1 or 5 mm / min.
[0120]
[0122] Flexural modulus, flexural stress and flexural elongation: Flexural properties may be tested according to ISO Test No. 178:2010 (technically equivalent to ASTM D790-10). The test may be performed on a support span of 64 mm. The test may be performed on the center of an uncut ISO 3167 multipurpose bar. The test temperature may be about 23°C and the test speed may be 2 mm / min.
[0121]
[0123] Unnotched and Notched Charpy Impact Strength: Charpy properties may be tested according to ISO Test No. ISO179-1:2010 (technically equivalent to ASTM D256-10, Method B). This test may be performed using a Type 1 specimen size (80 mm length, 10 mm width, and 4 mm thickness). When testing notched impact strength, the notch may be a Type A notch (0.25 mm base radius). Specimens may be cut from the center of the multipurpose bar using a single-tooth milling machine. The test temperature may be about 23°C.
[0122]
[0124] Dielectric constant ("Dk") and dissipation factor ("Df"): The dielectric constant (or relative static permittivity) and dissipation factor are determined by Baker-Jarvis et al., IEEE Trans. on Dielectric and Electrical Insulation, 5(4), 571 (1998) and Krupka et al., Proc. th It is determined using a known split-post dielectric resonance method such as that described in International Conference on Dielectric Materials: Measurements and Applications, IEEE Conference Publication No. 430 (September 1996). More specifically, a plate-shaped sample of size 80 mm x 80 mm x 1 mm was inserted between two fixed dielectric resonators. The resonators measured the dielectric constant components in the plane of the specimen. Five samples were tested and the average value was recorded. Using the split-post resonator, dielectric measurements can be made in the low gigahertz range, e.g., 1, 2 or 10 GHz.
[0123]
[0125] Thermal cycling test: The specimen is placed in a temperature controlled chamber and heated / cooled within a temperature range of -30°C to 100°C. The specimen is first heated until it reaches a temperature of 100°C, at which point it is immediately cooled. When the temperature reaches -30°C, the specimen is immediately heated again until it reaches 100°C. 23 heating / cooling cycles may be performed over a 3 hour period.
[0124] Example 1
[0126] Samples 1 to 5 were prepared by mixing liquid crystal polymers (LCP1, LCP2, LCP3, or LCP4), titanium dioxide, graphite, and copper chromite filler (CuCr 2 O 4 The LCPs are made from various combinations of 100% NDA, 10% glass fiber, and 10% alumina trihydrate. LCP1 is made from 48% HNA, 2% HBA, 25% BP, and 25% TA. LCP2 is made from 43% HBA, 20% NDA, 9% TA, and 28% HQ. LCP3 is made from 73% HBA, and 27% HNA. LCP4 is made from 60% HBA, 4% HNA, 18% TA, and 18% BP. Compounding was performed using an 18 mm single screw extruder. Parts are injection molded and samples are cut into plaques (60 mm x 60 mm).
[0125] [Table 1]
[0126]
[0127] Samples 1-5 were tested for thermal and mechanical properties and the results are listed in Table 2 below.
[0127] [Table 2]
[0128] Example 2 Samples 6-10 are made from various combinations of liquid crystal polymers (LCP1, LCP2 or LCP3), titanium dioxide, graphite or carbon fiber, glass fiber, alumina trihydrate and PPS. Compounding was carried out using an 18 mm single screw extruder. Parts were injection molded and samples were molded into plaques (60 mm x 60 mm).
[0129] [Table 3]
[0130]
[0129] Samples 6-10 were tested for thermal and mechanical properties, and the results are listed in Table 4 below.
[0131] [Table 4]
[0132] Example 3
[0130] Samples 11 to 15 were prepared by mixing liquid crystal polymer (LCP2, LCP3 or LCP4), titanium dioxide, graphite, copper chromite filler (CuCr 2 O 4 The composites are made from various combinations of cellulose acetate, glass fiber, and alumina trihydrate. Compounding was carried out using an 18 mm single screw extruder. Parts are injection molded and samples are cut into plaques (60 mm x 60 mm).
[0133] [Table 5]
[0134]
[0131] Samples 11-15 were tested for thermal and mechanical properties, and the results are listed in Table 6 below.
[0135] [Table 6]
[0136] Example 4
[0132] Samples 16 to 22 were prepared by mixing liquid crystal polymers (LCP2, LCP3, or LCP4), graphite, carbon fiber, copper chromite filler (CuCr 2 O 4 The composites are made from various combinations of cellulose acetate, cellulose ether, and glass fibers. Compounding was carried out using an 18 mm single screw extruder. Parts are injection molded and samples are cut into plaques (60 mm x 60 mm).
[0137] [Table 7]
[0138]
[0133] Samples 16-22 were tested for thermal and mechanical properties, and the results are set forth in Table 8 below.
[0139] [Table 8]
[0140] Example 5
[0134] Samples 23 to 27 were prepared by mixing liquid crystal polymers (LCP2, LCP3, or LCP4), copper chromite (CuCr 2 O 4 ), glass fiber, zinc oxide single crystal, tetrapod whisker (Pana-Tetra™ manufactured by Panasonic), conductive graphite and / or semiconductive graphite (Krefine™ manufactured by Kureha Extron, volume resistivity 3×10 7 The materials were formulated from various combinations of modulus (ohm·cm). Compounding was carried out using an 18 mm single screw extruder. Parts were injection molded and samples were cut into plaques (60 mm × 60 mm).
[0141] [Table 9]
[0142]
[0135] Samples 23-27 were tested for electrical, thermal and mechanical properties, and the results are listed in Table 10 below.
[0143] [Table 10]
[0144]
[0136] Sample 27 was also subjected to the thermal cycling test described above. After the test, the dielectric constant was determined to be 11.36 and the dielectric loss tangent was determined to be 0.1566. Thus, the ratio of the dielectric constant after the thermal cycling test to the initial dielectric constant was 0.96, and the ratio of the initial dielectric loss tangent to the dielectric loss tangent after the thermal cycling test was 0.75.
[0145] Example 6
[0137] Samples 28 to 31 were prepared by mixing liquid crystal polymer (LCP2, LCP3 or LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr 2 O 4 The composites are made from various combinations of cellulose, cellulose acetate, cellulose ether, and glass fibers. Compounding was carried out using a 32 mm twin screw extruder. Parts are injection molded and samples are cut into plaques (80 mm x 90 mm x 3 mm).
[0146] [Table 11]
[0147]
[0138] Samples 28-31 were tested for thermal and mechanical properties, and the results are listed in Table 12 below.
[0148] [Table 12]
[0149] Example 7
[0139] Samples 32 to 37 were prepared by mixing liquid crystal polymers (LCP2, LCP3, or LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr 2 O 4 The composites are made from various combinations of cellulose, cellulose acetate, cellulose ether, and glass fibers. Compounding was carried out using a 32 mm twin screw extruder. Parts are injection molded and samples are cut into plaques (80 mm x 90 mm x 3 mm).
[0150] [Table 13]
[0151]
[0140] Samples 32-37 were tested for thermal and mechanical properties, and the results are set forth in Table 14 below.
[0152] [Table 14]
[0153]
[0141] Samples 35 to 37 were also subjected to the thermal cycling test described above. After the test, the dielectric loss tangents obtained for the samples were determined to be 0.01764, 0.0155, and 0.0142, respectively. Thus, the ratios of the dielectric loss tangent after the thermal cycling test to the initial dielectric loss tangent for samples 35, 36, and 37 were 0.84, 0.91, and 0.89, respectively.
[0154] Example 8
[0142] Samples 38 to 44 were prepared by mixing liquid crystal polymers (LCP2 and LCP4), copper chromite filler (CuCr 2 O 4 The composites are made from various combinations of PTFE, glass fiber, alumina trihydrate ("ATH"), lubricant (polyethylene wax), and polytetrafluoroethylene (PTFE1 and PTFE2). PTFE1 is a powder of polytetrafluoroethylene particles with a D50 particle size of 4 μm, and PTFE2 is a powder of polytetrafluoroethylene particles with a D50 particle size of 40 μm. Compounding was performed using an 18 mm single screw extruder. Parts are injection molded and samples are cut into plaques (60 mm x 60 mm).
[0155] [Table 15]
[0156]
[0143] Samples 38-44 were tested for thermal and mechanical properties, and the results are set forth in Table 16 below.
[0157] [Table 16]
[0158] Example 9
[0144] Samples 45 to 47 were prepared by mixing liquid crystal polymers (LCP2, LCP3, or LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr 2 O 4 The composites are made from various combinations of cellulose, cellulose acetate, cellulose ether, and glass fibers. Compounding was carried out using a 32 mm twin screw extruder. Parts are injection molded and samples are cut into plaques (80 mm x 90 mm x 3 mm).
[0159] [Table 17]
[0160]
[0145] Samples 45-47 were tested for thermal and mechanical properties, and the results are set forth in Table 18 below.
[0161] [Table 18]
[0162]
[0146] Samples 45-47 were also subjected to the thermal cycle test described above. After the test, the dielectric constants obtained for the samples were determined to be 14.1, 13.2 and 16.6, respectively. Thus, the ratios of the dielectric constants after the thermal cycle test to the initial dielectric constants of samples 45, 46 and 47 were 0.99, 0.99 and 0.98, respectively. Also, the dielectric loss tangents obtained for the samples were determined to be 0.020, 0.020 and 0.021, respectively. Thus, the ratios of the dielectric loss tangent after the thermal cycle test to the initial dielectric loss tangent of samples 45, 46 and 47 were 1.18, 1.18 and 1.10, respectively.
[0163] Example 10
[0147] Sample 48 was prepared by mixing liquid crystal polymers (LCP2, LCP3 and LCP4), alumina trihydrate (ATH), titanium dioxide, carbon fiber, copper chromite filler (CuCr 2 O 4The composites are made from various combinations of cellulose, cellulose acetate, cellulose ether, and glass fibers. Compounding was carried out using a 32 mm twin screw extruder. Parts are injection molded and samples are cut into plaques (80 mm x 90 mm x 3 mm).
[0164] [Table 19]
[0165]
[0148] Sample 48 was tested for thermal and mechanical properties and the results are set forth in Table 20 below.
[0166] [Table 20]
[0167] Example 11
[0149] Sample 49 is formed from liquid crystal polymers (LCP1 and LCP4), hollow glass spheres, glass powder, glass fiber, and alumina trihydrate. The glass powder had a relative dielectric constant of 4.8 determined at a frequency of 1 GHz. Compounding was carried out using a 25 mm single screw extruder.
[0168] [Table 21]
[0169]
[0150] The samples were then tested for thermal and mechanical properties, and the results are set forth in Table 22 below.
[0170] [Table 22]
[0171]
[0151] These and other modifications and variations of the present invention are intended to be within the spirit and scope of the present invention. It will be understood that the present invention can be practiced by those skilled in the art without departing from the spirit and scope of the present invention. Moreover, it should be understood that aspects of the various embodiments may be interchanged both in whole or in part. Moreover, those skilled in the art will appreciate that the foregoing description is merely illustrative, and thus does not limit the invention as further described in the appended claims. The claims as filed are set forth below. [Claim 1] substrate; at least one antenna element configured to transmit and receive 5G radio frequency signals and coupled to the substrate; 1. A 5G antenna system comprising: 1. A 5G antenna system, wherein the substrate comprises a polymer composition comprising a polymer matrix containing at least one polymer having a glass transition temperature of about 30° C. or greater, and at least one laser activatable additive, and further wherein the polymer composition exhibits a dielectric loss tangent of about 0.1 or less, determined at a frequency of 2 GHz. [Claim 2] 10. The 5G antenna system of claim 1, wherein at least one antenna element has a feature size of less than about 1,500 micrometers. [Claim 3] 3. The 5G antenna system of claim 1 or 2, wherein the 5G radio frequency signal has a frequency greater than about 28 GHz. [Claim 4] 4. The 5G antenna system of claim 1, wherein the at least one antenna element comprises a plurality of antenna elements arranged in an antenna array. [Claim 5] 5. The 5G antenna system of claim 4, wherein the plurality of antenna elements are separated by a spacing distance of less than about 1,500 micrometers. [Claim 6] 5. The 5G antenna system of claim 4, wherein the plurality of antenna elements includes at least 16 antenna elements. [Claim 7] 7. The 5G antenna system of claim 6, wherein the plurality of antenna elements are arranged in a grid. [Claim 8] 5. The 5G antenna system of claim 4, wherein the antenna array is configured for at least eight transmit channels and at least eight receive channels. [Claim 9] 5. The 5G antenna system of claim 4, wherein the antenna array has an average antenna element density of greater than 1,000 antenna elements per square centimeter. [Claim 10] 10. The 5G antenna system of claim 1, further comprising a base station, the base station comprising at least one antenna element. [Claim 11] 11. A 5G antenna system according to any preceding claim, further comprising at least one of a user computing device or a repeater, wherein at least one of the user computing device or the repeater base station comprises at least one antenna element. [Claim 12] 12. The 5G antenna system of claim 1, wherein the polymer comprises a polyamide, a polyester, a polyarylene sulfide, a polyaryl ketone or a mixture thereof. [Claim 13] 13. The 5G antenna system of claim 12, wherein the polymer comprises a polyester including a thermotropic liquid crystal polymer. [Claim 14] 14. The 5G antenna system of claim 1, wherein the polymer composition further comprises a laser activatable additive. [Claim 15] The laser activatable additive has the following general formula: A.B. 2 O 4 (In the formula, A is a metal cation having a valence of 2; B is a metal cation having a valence of 3. 15. The 5G antenna system of claim 14, comprising a spinel crystal having the following formula: [Claim 16] Spinel crystals are MgAl2 O 4 , ZnAl 2 O 4 , FeAl 2 O 4 , CuFe 2 O 4 , CuCr 2 O 4 , MnFe 2 O 4 , NiFe 2 O 4 , TiFe 2 O 4 , FeCr 2 O 4 , MgCr 2 O 4 15. The 5G antenna system of claim 14, comprising: [Claim 17] 17. The 5G antenna system of any of claims 1 to 16, wherein the polymer composition further comprises a fibrous filler. [Claim 18] 20. The 5G antenna system of claim 17, wherein the fibrous filler comprises glass fiber. [Claim 19] 19. The 5G antenna system of claim 1 , wherein the polymer composition further comprises a dielectric material. [Claim 20] Dielectric materials have a capacitance of about 0.1 ohm cm to about 1×10 12 20. The 5G antenna system of claim 19 having a volume resistivity of ohm-cm. [Claim 21] 21. The 5G antenna system of claim 20, wherein the dielectric material comprises an inorganic oxide material. [Claim 22] 22. The 5G antenna system of claim 21 , wherein the inorganic oxide material comprises titanium dioxide particles. [Claim 23] 22. The 5G antenna system of claim 21 , wherein the inorganic oxide material comprises inorganic oxide whiskers. [Claim 24] 24. The 5G antenna system of claim 23, wherein the whiskers are zinc oxide whiskers. [Claim 25] 24. The 5G antenna system of claim 23, wherein the whisker has a central body and a plurality of needle-like crystals extending radially therefrom. [Claim 26] 21. The 5G antenna system of claim 20, wherein the dielectric material comprises an inorganic oxide material having a volume resistivity of 0.1 ohm·cm to about 500 ohm·cm. [Claim 27] Dielectric material is about 1×10 3 ~Approx. 1×10 12 21. The 5G antenna system of claim 20, comprising a carbon material having a volume resistivity of ohm·cm. [Claim 28] The dielectric material is a conductive material having a volume resistivity of less than about 0.1 ohm cm and a dielectric constant of less than about 1×10 12 21. The 5G antenna system of claim 20, comprising an insulating material having a volume resistivity greater than ohm·cm. [Claim 29] 29. The method of claim 28, wherein the conductive material comprises a carbon material and the insulating material comprises an inorganic oxide material. 5G antenna system. [Claim 30] 30. The 5G antenna system of any of claims 1 to 29, wherein the polymer composition further comprises a laser activatable additive, a fibrous filler, and a dielectric material, and wherein the ratio of the weight percentage of the fibrous filler to the combined weight percentage of the dielectric material and the laser activatable additive is from about 0.05 to about 1. [Claim 31] 31. The 5G antenna system of any one of claims 1 to 30, wherein the polymer composition comprises about 15 wt.% to about 85 wt.% of the thermotropic liquid crystal polymer and about 0.1 wt.% to about 30 wt.% of the laser activatable additive. [Claim 32] 32. The 5G antenna system of any of claims 1 to 31, wherein the polymer composition comprises a hydrophobic material. [Claim 33] 33. The 5G antenna system of claim 32, wherein the hydrophobic material comprises a fluoropolymer. [Claim 34] 34. The 5G antenna system of any of claims 1 to 33, wherein the polymer composition comprises a hollow filler. [Claim 35] 35. The 5G antenna system of any of claims 1 to 34, wherein the polymer composition exhibits a relative dielectric constant of about 4 or greater, determined at a frequency of 2 GHz. [Claim 36] The polymer composition is -1 36. The 5G antenna system of claim 1, having a melt viscosity of about 5 to about 150 Pa·s determined at a shear rate of 100 Hz and a temperature of 350° C.
Claims
1. substrate; at least one antenna element coupled to the substrate, the antenna element configured to transmit and receive 5G radio frequency signals; 1. A 5G antenna system comprising:
5. A 5G antenna system, wherein the substrate comprises a polymeric composition comprising a polymeric matrix containing at least one polymer having a glass transition temperature of about 30° C. or greater, at least one laser activatable additive, and a dielectric material, the dielectric material comprising carbon fiber or having a volume resistivity of about 0.1 ohm-cm to about 1×10 12 ohm-cm, and further wherein the polymeric composition exhibits a dielectric loss tangent of about 0.1 or less and a relative dielectric constant of about 10 or greater, determined at a frequency of 2 GHz.
2. The 5G antenna system of claim 1, wherein the spacing between the antenna elements or the width of the antenna elements is less than about 1,500 micrometers.
3. A 5G antenna system as described in any of claims 1 to 2, wherein the at least one antenna element includes a plurality of antenna elements arranged in an antenna array.
4. The 5G antenna system of claim 3, wherein the multiple antenna elements are separated by a spacing distance of less than about 1,500 micrometers.
5. The 5G antenna system of claim 3, wherein the plurality of antenna elements includes at least 16 antenna elements.
6. The 5G antenna system of claim 5, wherein the multiple antenna elements are arranged in a grid.
7. The 5G antenna system of claim 3, wherein the antenna array is configured for at least eight transmit channels and at least eight receive channels.
8. The 5G antenna system of claim 3, wherein the antenna array has an average antenna element density of greater than 1,000 antenna elements per square centimeter.
9. 9. The 5G antenna system of claim 1 , further comprising a base station, the base station comprising the at least one antenna element.
10. 10. The 5G antenna system of claim 1, further comprising at least one of a user computing device or a repeater, wherein at least one of the user computing device or the repeater comprises the at least one antenna element.
11. A 5G antenna system as described in any one of claims 1 to 10, wherein the polymer comprises a polyamide, a polyester, a polyarylene sulfide, a polyaryl ketone or a mixture thereof.
12. The 5G antenna system of claim 11, wherein the polymer comprises a polyester including a thermotropic liquid crystal polymer.
13. A 5G antenna system as described in any one of claims 1 to 12, wherein the polymer composition comprises from about 0.5% to about 20% by weight of the laser activatable additive.
14. The laser activatable additive of claim 1, wherein the laser activatable additive has the following general formula: AB 2 O 4 (In the formula, A is a metal cation having a valence of 2; B is a metal cation having a valence of 3.
13. The 5G antenna system of claim 1, comprising a spinel crystal having
15. The spinel crystal is MgAl 2 O 4 , ZnAl 2 O 4 , FeAl 2 O 4 , CuFe 2 O 4 , CuCr 2 O 4 , MnFe 2 O 4 , NiFe 2 O 4 , TiFe 2 O 4 , FeCr 2 O 4 , MgCr 2 O 4 15. The 5G antenna system of claim 14, comprising:
16. A 5G antenna system as described in any one of claims 1 to 15, wherein the polymer composition further comprises a fibrous filler.
17. The 5G antenna system of claim 16, wherein the fibrous filler comprises glass fiber.
18. The dielectric material has a thickness of about 0.1 ohm cm to about 1×10 12 10. The 5G antenna system of claim 1 having a volume resistivity of ohm-cm.
19. The 5G antenna system of claim 18, wherein the dielectric material comprises an inorganic oxide material.
20. The 5G antenna system of claim 19, wherein the inorganic oxide material comprises titanium dioxide particles.
21. The 5G antenna system of claim 19, wherein the inorganic oxide material comprises inorganic oxide whiskers.
22. The 5G antenna system of claim 21, wherein the whiskers are zinc oxide whiskers.
23. The 5G antenna system of claim 21, wherein the whisker has a central body and a plurality of needle-shaped crystals extending radially therefrom.
24. The 5G antenna system of claim 18, wherein the dielectric material comprises an inorganic oxide material having a volume resistivity of 0.1 ohm-cm to about 500 ohm-cm.
25. The dielectric material has a thickness of about 1×10 3 ~Approx. 1×10 12 20. The 5G antenna system of claim 18 comprising a carbon material having a volume resistivity of ohm-cm.
26. The dielectric material comprising a conductive material having a volume resistivity of less than about 0.1 ohm-cm and a dielectric constant of less than about 1×10 12 20. The 5G antenna system of claim 18 including an insulating material having a volume resistivity greater than ohm-cm.
27. The 5G antenna system of claim 26, wherein the conductive material comprises a carbon material and the insulating material comprises an inorganic oxide material.
28. A 5G antenna system as described in any of claims 1 to 27, wherein the polymer composition further comprises a fibrous filler, and the ratio of the weight percentage of the fibrous filler to the combined weight percentage of the dielectric material and the laser activatable additive is from about 0.05 to about 1.
29. The 5G antenna system of any one of claims 1 to 28, wherein the polymer composition comprises about 15 wt.% to about 85 wt.% of a thermotropic liquid crystal polymer and about 0.1 wt.% to about 30 wt.% of the laser activatable additive.
30. A 5G antenna system as described in any one of claims 1 to 29, wherein the polymer composition comprises a hydrophobic material.
31. The 5G antenna system of claim 30, wherein the hydrophobic material comprises a fluoropolymer.
32. A 5G antenna system as described in any one of claims 1 to 31, wherein the polymer composition comprises a hollow filler.
33. A 5G antenna system as described in any one of claims 1 to 32, wherein the polymer composition exhibits a dielectric constant of greater than or equal to about 15 determined at a frequency of 2 GHz.
34. The polymer composition according to claim 1,000 sec. -1 34. The 5G antenna system of any of claims 1 to 33, having a melt viscosity of about 5 to about 150 Pa s determined at a shear rate of 0.05 to 0.5 Pa s and a temperature of 350 °C.
Citation Information
Patent Citations
Thermoplastic composition for use in forming laser-direct structured substrates
JP2015502418A
Multi-antenna module and portable terminal
JP2019080298A
Electronic Module for Use in an Automotive Vehicle
US20190159371A1